Adhesive tape with a cross-linked polyurethane carrier
By using crosslinked polyurethane carrier and vinyl aromatic block copolymer pressure-sensitive adhesive layer in the tape, the problem of high force and easy damage during peeling is solved, and a low force, residual and damage-free peeling effect is achieved.
Patent Information
- Application Number
- CN202211121687.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-16
- Filing Date
- 2022-09-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-09-15
AI Technical Summary
Existing tapes require a greater force when peeling, resulting in the potential damage to sensitive components in electronics manufacturing and it is difficult to ensure residual and damage-free peeling.
Releasable tape using a crosslinked polyurethane carrier and a pressure-sensitive adhesive layer based on a vinyl aromatic block copolymer is achieved by stretching and peeling, low force peeling and retaining adhesion.
The adhesive tape is peeled off without residue and damage under low force conditions, ensuring that the adhesive surface of the components to be bonded is not damaged in electronic device manufacturing.
Smart Images

Figure GDA0004908495530000051 
Figure GDA0004908495530000061 
Figure GDA0004908495530000351
Abstract
Description
Technical Field
[0001] The invention relates to a re-peelable adhesive tape having a carrier based on a crosslinked polyurethane and an adhesive layer based on a vinyl aromatic block copolymer, a process for producing the adhesive tape and the use of the adhesive tape in the production of electronic components. Background Art
[0002] Re-peelable adhesive tapes have long been established on the market and are known to the person skilled in the art.
[0003] Thus, EP 0 816 459 describes adhesive film strips for removable bonding, which have a layer structure consisting of an elastic carrier layer provided with an adhesive layer on one or both sides, wherein both carrier layer and adhesive layer comprise as base polymer a styrene block copolymer blended with a tackifier resin which is compatible with the elastomeric blocks of the styrene block copolymer used, these strips being able to be peeled off without damage and residue by pulling in the direction of the bonding plane.
[0004] DE 10 2015 206 076 relates to an adhesive strip consisting of one or more adhesive layers, all of which consist of a pressure-sensitive adhesive foamed with microspheres, which can be peeled off again without residue or damage by extensive stretching substantially in the bonding plane. DE 10 2016 223 852 discloses a pressure-sensitive adhesive strip comprising at least one adhesive layer foamed with microspheres and at least one carrier B, which can be peeled off again without residue or damage by extensive stretching substantially in the bonding plane.
[0005] Re-peelable tapes have also recently gained ground in the electronics industry, where they are used to bond components in electronic devices. However, the difficulty that arises here is that a balance must be found between sufficient peel adhesion and the re-peelability of the tape to prevent damage to the in some cases sensitive components when the tape is re-peeled.
[0006] WO 2015 / 135134 describes a stretch-peelable adhesive tape comprising a carrier and a first pressure-sensitive adhesive layer applied on at least one surface of the carrier, the tape having a thickness between 0.05 and 0.1 mm and a longitudinal elongation of 850% to 2200%, the tape being firmly bonded to a substrate and being repeelable from the substrate by being able to be peeled off from the substrate surface at an angle of 90° or more without tearing and without leaving any substantial residue on the substrate, the pressure-sensitive adhesive being formed from an acrylate copolymer containing terminal functional polyurethane groups. The tape is also said to be useful for electronic devices.
[0007] Although adhesive tapes from the prior art have proven suitable also for electronics, they have the disadvantage that in some cases great forces have to be applied to remove the tape, with the result that damage-free separation from the components bonded with the tape is not ensured.
[0008] Against this background, the problem underlying the present invention was to provide an adhesive tape which can be peeled off again with relatively low forces and which at the same time has sufficient peel adhesion to produce a strong bond between the parts to be bonded. Summary of the invention
[0009] Surprisingly it was found that this problem is solved by an adhesive tape as defined in the first subject matter of the invention. Preferred developments of the adhesive tape of the invention are set forth in the dependent claims.
[0010] Therefore, a first subject of the present invention is an adhesive tape removable by stretching, comprising:
[0011] a) at least one carrier based on a crosslinked polyurethane; and
[0012] b) at least one layer of pressure-sensitive adhesive based on a vinyl aromatic block copolymer.
[0013] In the present invention, it was surprisingly found that the adhesive tape of the present invention is contrary to the existing prejudice that crosslinking of the carrier reduces its stretchability and increases the force that must be applied in order to peel the adhesive tape. This effect is not observed with the adhesive tape of the present invention. On the contrary, it has been found that the adhesive tape of the present invention exhibits a consistently low tensile strength during the peeling process while increasing the maximum elongation and the maximum breaking force, meaning that the force required to peel the adhesive tape is low, and at the same time little or no tearing of the adhesive tape is observed in application tests.
[0014] The invention relates to adhesive tapes in any manufactured form, preferably adhesive tape rolls. The adhesive tape, especially the adhesive tape in web form, can be manufactured in roll form (i.e. in the form of an Archimedean spiral wound onto itself) or as adhesive strips of the kind obtained, for example, in the form of die-cut pieces.
[0015] The adhesive tape of the invention is more particularly in the form of a web. A web is an object whose length (extent in the x-direction) is a multiple of its width (extent in the y-direction) and whose width is approximately uniform, preferably completely uniform, along the entire length.
[0016] In the sense of the invention, the general expressions "adhesive tape" and synonymously "adhesive strip" also include all sheet-like structures, such as two-dimensionally extending films or film segments, tapes, tape segments, etc. with extended length and limited width, and finally die-cut parts or labels.
[0017] The adhesive tape has a longitudinal extent (x direction) and a transverse extent (y direction). The adhesive tape also has a thickness (z direction) extending perpendicular to the two extents, wherein the transverse extent and the longitudinal extent are multiple times greater than the thickness. The thickness is largely the same, preferably completely the same, over the entire surface extent of the adhesive tape, which extent is defined by the length and the width.
[0018] The external exposed surface of the pressure-sensitive adhesive layer of the adhesive tape of the present invention can be advantageously provided with a non-stick material, such as a peeling (release) paper or a peeling film, also referred to as a liner. The liner can also be a material having a non-stick coating on at least one side, preferably on both sides, such as a double-sided siliconized material. The liner or more generally a temporary carrier prepared is not a part of the adhesive tape, but is merely a means (tool) for the manufacture, storage and / or further processing of the adhesive tape by die cutting. In addition, unlike a permanent carrier, the liner is not fixedly joined to the adhesive layer, but acts as a temporary carrier, i.e. a carrier that can be removed from the adhesive layer. In the present application, a "permanent carrier" is also simply referred to as a "carrier" synonymously.
[0019] Since the adhesive tape of the present invention includes a pressure-sensitive adhesive, the adhesive tape of the present invention is also referred to as a pressure-sensitive adhesive tape.
[0020] As described above, the adhesive tapes according to the invention can be peeled off again without leaving residue or without destruction by stretching. "Peeling off without leaving residue" as applied to the adhesive tapes according to the invention means that they do not leave any adhesive residues on the adhesive surfaces of the components when peeling off. Furthermore, "peeling off without destruction" of the adhesive tapes according to the invention means that they do not damage (e.g. destroy) the adhesive surfaces of the components when peeling off. DETAILED DESCRIPTION
[0021] a) Carrier
[0022] The carrier used in the pressure-sensitive adhesive tape of the present invention is a carrier based on crosslinked polyurethane. The polyurethane-based carrier is preferably a polyurethane prepared by extrusion (TPU) or a polyurethane prepared by dispersion (PUD). The polyurethane carrier can also be prepared by solution.
[0023] The carrier preferably has a force F at 400% extension of at most 45%, preferably at most 40%. 400% and the breaking force F 断裂 Ratio.
[0024] The crosslinking agent is preferably present in an amount of 0.5 to 10 wt%, more preferably 1.0 to 8 wt%, more particularly 1.5 to 5 wt%, based on the total weight of the carrier.
[0025] The carrier layer of the invention has mechanical properties suitable for use in adhesive tapes that can be peeled off by extensive stretching. The carrier layer preferably has a longitudinal elongation at break of at least 600%, more preferably at least 800%.
[0026] The support layer may be opaque, tinted, optically clear, or transparent.
[0027] i) Thermoplastic polyurethane (TPU)
[0028] In a first embodiment, the carrier of the adhesive tape comprises at least one, preferably exactly one, layer based on crosslinked thermoplastic polyurethane, which has typically been produced by extrusion. Such a layer based on thermoplastic polyurethane typically means a layer with a thermoplastic polyurethane fraction of at least 50% by weight. The fraction of thermoplastic polyurethane in this layer is preferably at least 90% by weight, and more particularly, the layer consists essentially of thermoplastic polyurethane.
[0029] The crosslinked thermoplastic polyurethane of at least one carrier layer is preferably based on polyester, but can alternatively be based on polyether, for example based on polyTHF as polyol. Polyester-based or polyether-based thermoplastic polyurethanes are typically thermoplastic polyurethanes based on aliphatic polyesters or aliphatic polyethers, respectively. The glass transition temperature (T g ) is preferably between -20°C and 40°C, and the glass transition temperature of the hard molecular chain of the thermoplastic polyurethane is preferably between 60 and 110°C. The thermoplastic polyurethane typically has a tensile strength of greater than 20, preferably greater than 35 MPa, and a Shore A hardness preferably between 55 and 85, such as more particularly between 55 and 70. In an alternative preferred embodiment, the Shore A hardness is between 70 and 85.
[0030] The thermoplastic polyurethane is preferably the reaction product of a reaction mixture comprising at least one diisocyanate, at least one polyester polyol (or polyether polyol), a crosslinker and optionally at least one chain extender, the polyester polyol or polyether polyol typically having a melting temperature of at least 30° C., such as at least 100° C. or at least 200° C. For example, selecting appropriate processing operations, such as cooling conditions, can help to increase the crystallinity of the layer. The crystallinity can be determined by differential scanning calorimetry (DSC) and expressed as the fraction of crystallinity in the thermoplastic polyurethane film.
[0031] The fraction of diisocyanate in the reaction mixture is preferably 0.5-47% by weight, more preferably 1-40% by weight, more particularly 10-25% by weight. The amount of diisocyanate in the reaction mixture can also be expressed as an isocyanate index. The isocyanate index is generally understood to refer to the ratio of the equivalents of isocyanate functional groups used to the equivalents of hydroxyl functional groups. The isocyanate index of the reaction mixture is preferably a ratio of 0.99 to 1.20, for example 1.00 to 1.10.
[0032] The diisocyanate is preferably a diisocyanate having a structure according to Formula I
[0033] O=C=NRN=C=O (Formula I),
[0034] Wherein R is selected from substituted or unsubstituted (C1-C 40 )-alkylene, (C2-C 40 )-alkenylene, (C4-C 20 )-arylene, (C4-C 20 )-arylene-(C1-C 40 )-alkylene-(C4-C 20 )-arylene, (C4-C 20 )-cycloalkylene and (C4-C 20)-aralkylene. In another example, the diisocyanate is selected from dicyclohexylmethane 4,4'-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 1,4-phenylene diisocyanate, 1,3-phenylene diisocyanate, meta-xylylene diisocyanate, tolylene 2,4-diisocyanate, tolylene 2,6-diisocyanate, poly(hexamethylene diisocyanate), 1,4-cyclohexylene diisocyanate, 4-chloro-6-methyl-1,3-phenylene diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,4-diisocyanato (diisocyanato) butane, 1,8-diisocyanato octane, 2,6-toluene diisocyanate, 2,5-toluene diisocyanate, 2,4-toluene diisocyanate, meta-phenylene diisocyanate, Isocyanate, p-phenylene diisocyanate, methylene bis(o-chlorophenyl diisocyanate), methylene diphenylene 4,4'-diisocyanate, (4,4'-diisocyanato-3,3',5,5'-tetraethyl) diphenylmethane, 4,4'-diisocyanato-3,3'-dimethoxy-biphenyl (o-dianisidine diisocyanate), 5-chloro-2,4-toluene diisocyanate, 1-chloromethyl -2,4-diisocyanatobenzene, tetramethyl-m-xylylene diisocyanate, 1,6-diisocyanatohexane, 1,12-diisocyanatododecane, 2-methyl-1,5-diisocyanatopentane, methylene dicyclohexyl 4,4'-diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 2,2,4-trimethylhexyl diisocyanate or a mixture thereof.
[0035] Particularly preferred diisocyanates are diphenylmethane 4,4′-diisocyanate (MDI), hexane diisocyanate (HDI), isophorone diisocyanate (IPDI) or hexamethylene diisocyanate (HMDI).
[0036] The fraction of polyester polyol or polyether polyol in the reaction mixture is preferably in the range from 43% to 70% by weight, more preferably from 50% to 60% by weight.
[0037] Polyester polyols can contain any suitable number of hydroxyl groups. Polyester polyols can, for example, contain four hydroxyl groups or three hydroxyl groups. Polyester polyols can even contain two hydroxyl groups, thus making the polyester polyols polyester diols. Typically, polyester polyols can be the product of a condensation reaction such as a polycondensation reaction. However, polyester polyols are typically not prepared via a ring-opening polymerization product.
[0038] In the example of preparing polyester polyols by condensation reaction, the reaction can occur between one or more carboxylic acids and one or more polyols. Examples of suitable carboxylic acids include carboxylic acids of formula IIa (dicarboxylic acids) and IIb (hydroxycarboxylic acids) having the following structures:
[0039]
[0040] In Formula IIa, R 1 Typically selected from substituted or unsubstituted (C1-C 40 )-alkylene, (C2-C 40 )-alkenylene, (C4-C 20 )-arylene, (C4-C 20 )-cycloalkylene and (C4-C 20 )-aralkylene.
[0041]
[0042] In Formula IIb, R 2 Typically selected from substituted or unsubstituted (C1-C 40 )-alkylene, (C2-C 40 )-alkenylene, (C4-C 20 )-cycloalkylene and (C4-C 20 )-aralkylene.
[0043] Examples of suitable carboxylic acids include lactic acid (2-hydroxypropionic acid), succinic acid (succinic acid), 3-hydroxybutyric acid, 3-hydroxyvaleric acid, terephthalic acid (benzene-1,4-dicarboxylic acid), naphthalene dicarboxylic acid, 4-hydroxybenzoic acid, 6-hydroxynaphthalene-2-carboxylic acid, oxalic acid, malonic acid (propane diacid), adipic acid (hexane diacid), pimelic acid (heptane diacid), oxalic acid (ethoic acid), suberic acid (octanedioic acid), azelaic acid (nonane diacid), sebacic acid (decane diacid), glutaric acid (pentane diacid), dodecanedioic acid, tridecanedioic acid, hexadecanedioic acid, maleic acid, fumaric acid, glutaconic acid, 2-decene (di) acid, muconic acid, glutinic acid (glutinic acid), Acid, citraconic acid, mesaconic acid, itaconic acid, malic acid (2-hydroxysuccinic acid), aspartic acid (2-aminosuccinic acid), glutamic acid (2-aminoglutaric acid), tartaric acid (2,3-dihydroxysuccinic acid), diaminopimelic acid, saccharic acid, mesooxalic acid, oxalacetic acid, acetone dicarboxylic acid (3-oxoglutaric acid), arabinonic acid, phthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid or mixtures thereof. Adipic acid is particularly preferred.
[0044] One example of a suitable polyol includes a polyol of Formula III having the following structure:
[0045] HO-R2 -OH (Formula III)
[0046] In Formula III, R 2 Selected from substituted or unsubstituted (C1-C 40 )-alkylene, (C2-C 40 )-alkenylene, (C4-C 20 )-arylene, (C1-C 40 )-acyl group, (C4-C 20 )-cycloalkylene, (C4-C 20 )-aralkylene and (C1-C 40 )-alkyleneoxy.
[0047] The diol may, for example, have a weight average molecular weight in the range of 30 to 250 daltons, preferably 50 to 150 daltons. The diol component may contain any suitable number of carbons. The diol may, for example, have a number average number of 2 to 50 carbons, preferably 3 to 140 carbons. Examples of suitable diols include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol (1,2-propylene glycol), dipropylene glycol, tripropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, or a mixture thereof.
[0048] Particularly preferred polyester polyols are therefore polyalkylene adipates.
[0049] Conventionally used for film manufacturing is mainly related to multilayer blown film operation. In this case, the PE layer (i.e. polyethylene layer) and the actual TPU layer are manufactured as co-extruded film in the blown film operation (i.e., the PE layer acts as a support carrier to provide the required mechanical stability for the extrudate). In use, i.e., before manufacturing the adhesive tape, the PE support carrier is removed, meaning that it represents a temporary carrier. However, for manufacturing the corresponding blown film, many additives are required, such as anti-blocking agents (e.g., silica particles) and lubricating waxes, to prevent the PU film from clogging when bubbles burst in the blown film operation. The problem here is that TPU is still viscous about 1 hour after melting. Two facts (crystalline superstructure and additives, especially silica particles) lead to adverse effects on mechanical properties. The silicate particles (point defects) and crystalline superstructure (hard, non-flexible domains) in the film both lead to a reduction in stretchability, and particularly in use (i.e., when stretched over a wide range) a greater tearing tendency. Due to wax migration to the PSA surface, i.e., the surface of the pressure-sensitive adhesive, wax additionally leads to the problem of reduced peel strength, and also leads to the difficulty of anchoring PSA on the film. Additionally advantageous for high stretchability and low tearing tendency is a high molecular weight of the PU polymer in order to increase the toughness of the film.
[0050] The TPU-based carrier layer is therefore preferably free of additives such as antiblocking agents and waxes. Furthermore, preferably, the polyurethane has no crystalline superstructure, as indicated by a DSC peak >210°C.
[0051] In a preferred embodiment, the TPU-based carrier layer is foamed. The foaming is preferably carried out using microspheres. Suitable microspheres are described later below. Alternatively, chemical and / or physical foaming agents can also be used.
[0052] ii) Polyurethane obtained by dispersion (PUD)
[0053] In an alternative preferred embodiment, the carrier of the adhesive tape according to the invention comprises at least one, preferably exactly one, layer based on a crosslinked polyurethane, which has been produced as a dispersion using a crosslinking agent. Such a layer based on polyurethane is typically a layer with a polyurethane fraction of at least 50% by weight. The fraction of polyurethane in this layer is preferably at least 90% by weight. The polyurethane is typically thermoplastic.
[0054] The polyurethane consists more particularly of at least one polyisocyanate component and at least one polyol component and is therefore the reaction product of at least said components.
[0055] The polyurethane here is more preferably an aliphatic polyester-polyurethane or an aliphatic polyether-polyurethane, ie the polyurethane in this case is based on an aliphatic polyester or an aliphatic polyether.
[0056] At least one polyisocyanate component is preferably a diisocyanate. Aromatic diisocyanates such as toluene diisocyanate (TDI) (particularly preferred), p-phenylene diisocyanate (PPDI), 4,4'-diphenylmethane diisocyanate (MDI), p,p'-bisphenyl diisocyanate (BPDI) or in particular aliphatic diisocyanates such as isophorone diisocyanate (IPDI), 1,6-hexamethylene diisocyanate (HDI) or 4,4'-diisocyanatodicyclohexylmethane (H12MDI) can be used. Also suitable are diisocyanates having substituents in the form of halo, nitro, cyano, alkyl, alkoxy, haloalkyl, hydroxyl, carboxyl, amide, amino or combinations thereof.
[0057] In general, it is possible to use all isocyanates which are known per se and are aliphatic, cycloaliphatic, araliphatic and preferably aromatic polyfunctional isocyanates.
[0058] Specific examples include the following: alkylene diisocyanates having 4 to 12 carbon atoms in the alkylene group, such as 1,12-dodecane diisocyanate, 2-ethyltetramethylene 1,4-diisocyanate, 2-methyl-pentamethylene 1,5-diisocyanate, tetramethylene 1,4-diisocyanate, and preferably hexamethylene 1,6-diisocyanate; cycloaliphatic diisocyanates, such as cyclohexane 1,3-diisocyanate and cyclohexane 1,4-diisocyanate and any desired mixtures of these isomers, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate), 2,4- and 2,6-hexahydrotolylene diisocyanate and any desired mixtures of these isomers. The organic diisocyanates and polyisocyanates are preferably selected from the group consisting of 2,4- and 2,6-tolylene diisocyanate and the corresponding isomer mixtures, 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate and the corresponding isomer mixtures, mixtures of 4,4'- and 2,4'-diphenylmethane diisocyanate, polyphenyl-polymethylene polyisocyanates, mixtures of 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate with polyphenyl-polymethylene polyisocyanates (crude MDI), and mixtures of crude MDI and tolylene diisocyanate. The organic diisocyanates and polyisocyanates can be used individually or in the form of mixtures thereof.
[0059] The polyisocyanate component preferably has a number average molecular weight of 60 to 50 000 g / mol, more particularly 400 to 10 000 g / mol, preferably 400 to 6000 g / mol.
[0060] So-called modified multifunctional isocyanates are also often used, which are products obtained by chemical reactions of organic diisocyanates and / or polyisocyanates. Examples include diisocyanates and / or polyisocyanates containing esters, ureas, biuret, allophanate, carbodiimide, isocyanurate, uretdione and / or carbamate groups. The specific examples considered include the following: organic polyisocyanates, preferably aromatic polyisocyanates, containing carbamate groups and having an NCO content of 33.6-15% by weight, preferably 31-21% by weight, based on their total weight. Examples are 2,4- and / or 2,6-toluene diisocyanate or crude MDI modified as follows: low molecular weight diols, triols, dialkylene glycols, trialkylene glycols or polyoxyalkylene glycols, which have a number average molecular weight of up to 6000 g / mol, more particularly up to 1500 g / mol. Examples of suitable di- and polyoxyalkylene glycols are diethylene, dipropylene, polyoxyethylene, polyoxypropylene and polyoxypropylene-polyoxyethylene diols, triols and / or tetraols. Also suitable are prepolymers comprising NCO groups, having an NCO content of 25 to 3.5% by weight, preferably 21 to 14% by weight, based on the total weight, prepared from polyester polyols and / or preferably polyether polyols with 4,4'-diphenylmethane diisocyanate, mixtures of 2,4'- and 4,4'-diphenylmethane diisocyanate, 2,4- and / or 2,6-tolylene diisocyanate or crude MDI. Furthermore, liquid polyisocyanates which contain carbodiimide groups and / or isocyanurate rings and have an NCO content of 33.6 to 15% by weight, preferably 31 to 21% by weight, based on the total weight, have proven useful, these polyisocyanates being based on, for example, 4,4′-, 2,4′- and / or 2,2′-diphenylmethane diisocyanate and / or 2,4- and / or 2,6-tolylene diisocyanate.
[0061] The modified polyisocyanates can be mixed with one another or with unmodified organic polyisocyanates such as 2,4′-, 4,4′-diphenylmethane diisocyanate, crude MDI, 2,4- and / or 2,6-tolylene diisocyanate.
[0062] Isocyanates which have been found to be suitable are diphenylmethane diisocyanate isomer mixtures or crude MDI, in particular crude MDI having a diphenylmethane diisocyanate isomer content of 30 to 55% by weight, and polyisocyanate mixtures containing urethane groups based on diphenylmethane diisocyanate having an NCO content of 15 to 33% by weight.
[0063] The preferred weight fraction of the polyisocyanate component is 10-40% by weight, more particularly 13-35% by weight and very preferably 15-30% by weight.
[0064] The polyol component in the present invention means not only a polymer having at least two hydroxyl groups but also generally means a compound having at least two hydrogen atoms reactive toward isocyanate.
[0065] The polyol component is preferably a diol, a polyether diol, a polyester diol, a polycarbonate diol, a polycaprolactone polyol or a polyacrylate polyol, more preferably a polyether diol, a polyester diol and a polycarbonate diol, and more particularly ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, cyclohexanediol, cyclohexyl dimethanol, octanediol, neopentyl glycol, diethylene glycol, triethylene glycol, trimethylpentanediol, benzenediol, benzene glycol, methylbenzene, bisphenol A, poly(butylene glycol-co-adipate) diol, poly(hexanediol-co-adipate) glycol, poly(ethylene glycol-co-adipate) glycol, polytetramethylene glycol, polypropylene glycol, polyethylene glycol or a mixture thereof.
[0066] The main function of the polyol component is to react with the polyisocyanate component to form a polyurethane polymer. However, in addition, the polyol component also acts as a physical regulator because the elasticity of the polyurethane depends on the molecular weight of the polyol component. The general rule is that the higher the molecular weight of the polyol component, the softer the resulting polyurethane.
[0067] The polyol component preferably has a number average molecular weight of 60 to 50 000 g / mol, more particularly 400 to 10 000 g / mol, preferably 400 to 6000 g / mol.
[0068] Polyurethane dispersions which can be used for the purposes of the present invention include in particular the following dispersions, optionally in combination:
[0069] a) Anionically stabilized aliphatic polyester-polyurethane dispersions (dispersions based on polyester and aliphatic anionic isocyanate-polyurethane). These include the following products sold by Covestro AG: LP RSC 1380, DL1537XP, DL 1554XP; Witcobond from Lanxess
[0070] 373-04; or from Stahl RU-92-410
[0071] b) Anionically stabilized aliphatic polyether-polyurethane dispersions. These include the following products sold by Covestro AG: 25LP DSB 1069; or Witcobond 386-53 from Lanxess
[0072] c) Anionically stabilized aliphatic polycarbonate-polyester-polyurethane dispersions. These include the following products sold by Covestro AG: DLU; or from Stahl EX-RU-92-600
[0073] d) Anionically stabilized polycarbonate-polyurethane dispersions. These include the following products sold by Covestro AG: DL2288XP.
[0074] Here, the polyurethane dispersion has a high solids fraction of preferably 30 to 70% by weight, more preferably 50 to 60% by weight. All products under a) to d) above typically contain no organic cosolvents.
[0075] The polyurethane dispersions of the present invention are aqueous. They are preferably free of organic solvents, but may optionally include organic solvents.
[0076] In order to adjust the properties of the polyurethane support being produced, it is advantageous if the starting mixture additionally comprises at least one further dispersion, which is typically selected from polyurethane dispersions, polyurethane dispersions whose polyol component contains comonomers having a flame retardant effect, synthetic rubber dispersions, natural rubber dispersions and polyacrylate dispersions. In this way, parameters including the stability of the polyurethane support and its elongation at break can be adjusted.
[0077] Polyacrylate dispersions include water-insoluble polyacrylates, which are typically dispersed in water by emulsifiers. They contain, for example, about 30 to 60% by weight of polyacrylate and about 3% by weight of emulsifier. The polyacrylate in the present invention is a water-insoluble polyacrylate, polymethacrylate, a mixture thereof or a copolymer with other monomers. The emulsifier may be an ionic, nonionic or steric (hindered) emulsifier. It is usually not fixedly introduced into the polymer chain. Acrylate dispersions may include additional additives, such as film formers or cosolvents, defoamers, flame retardants and / or wetting agents.
[0078] Acrylate dispersions are typically obtained by emulsion polymerization of suitable monomers. For this purpose, these monomers are finely dispersed in water using emulsifiers. In order to emulsify the monomers in water, a water-soluble free radical initiator is added. Since the free radicals formed by this initiator preferentially dissolve in water, their concentration in the monomer droplets is low, allowing the polymerization to proceed very uniformly in the droplets. After the polymerization is completed, the dispersion can be used directly, but is often mixed with additives such as defoamers, film formers and / or wetting agents to achieve further improvements in properties.
[0079] The reaction of the OH groups of the polyol component with the isocyanate groups can optionally be catalyzed. Catalysts considered include in particular the following:
[0080] Organometallic compounds, preferably organotin compounds, such as tin(II) salts of organic carboxylic acids, examples being tin(II) acetate, tin(II) octoate, tin(II) ethylhexanoate, tin(II) laurate, and dialkyltin(IV) salts of organic carboxylic acids, examples being dibutyltin diacetate, dibutyltin dilaurate, dibutyltin maleate, dioctyltin diacetate, and tertiary amines such as triethylamine, tributylamine, dimethylcyclohexylamine, dimethylbenzylamine, N-methylimidazole, N-methylmorpholine, N-ethylmorpholine, N-cyclohexylmorpholine, N,N,N' , N'-tetramethylethylenediamine, N,N,N',N'-tetramethylbutanediamine, N,N,N',N'-tetramethylhexylene-1,6-diamine, pentamethyldiethylenetriamine, tetramethyldiaminoethyl ether, bis(dimethylaminopropyl)urea, dimethylpiperazine, 1,2-dimethylimidazole, 1-azabicyclo-[3.3.0]-octane, 1,4-diazabicyclo[2.2.2]octane, and further alkanolamine compounds such as triethanolamine, triisopropanolamine, N-methyldiethanolamine and N-ethyldiethanolamine and dimethylethanolamine.
[0081] The catalysts under consideration further include: tris(dialkylamino)-s-hexahydrotriazines, more particularly tris-(N,N-dimethylamino)-s-hexahydrotriazine, tetraalkylammonium salts such as N,N,N-trimethyl N-(2-hydroxypropyl)(ammonium)formate, N,N,N-trimethyl-N-(2-hydroxypropyl)(ammonium)-2-ethylhexanoate, tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, alkali metal hydroxides such as sodium hydroxide, alkali metal alkoxides such as sodium methoxide and potassium isopropoxide, and alkali metal or alkaline earth metal salts of fatty acids having 1 to 20 carbon atoms and optionally OH side groups.
[0082] Preference is given to using tertiary amines, tin compounds, alkali metal and alkaline earth metal carboxylates, quaternary ammonium salts, s-hexahydrotriazines and tris(dialkylaminomethyl)phenols.
[0083] Preference is given to using from 0.001 to 5% by weight, more particularly from 0.002 to 2% by weight, of the catalyst or catalyst combination, based on the total weight of the starting mixture.
[0084] The polyurethane may optionally include a component containing active hydrogen and capable of forming hydrophilic groups, particularly preferably in an amount of 1-15% by weight, more particularly 3-10% by weight, and very preferably 4-7% by weight. Here, "active hydrogen" means that the hydrogen atoms of the component are unstable in the sense that they are easily able to undergo chemical reactions, such as substitution reactions, with other compounds so that hydrophilic groups can be formed. The effect of this component is that the polyurethane can be effectively dispersed in water. Particularly suitable hydrophilic groups include the following: -COO - 、-SO3 - 、-NR3 + or -(CH2CH2O) n The component containing active hydrogen may be, for example, dimethylolpropionic acid (DMPA), dimethylolbutyric acid (DMBA), polyethylene oxide, bis(hydroxyethyl)amine or sodium 3-bis(hydroxyethyl)aminopropanesulfonate.
[0085] As noted above, the active hydrogen-containing component is optional. For dispersion purposes, polyurethane dispersions often additionally or alternatively include at least one surfactant.
[0086] Particularly suitable surfactants (which also act as foam stabilizers) include in particular the following from the Bozzetto Group: STA (ammonium stearate) and SR (succinate).
[0087] However, also considered are additional surfactants which may in particular be selected from ether sulfates, fatty alcohol sulfates, sarcosinates, organic amine oxides, sulfonates, betaines, amides of organic acids, sulfosuccinates, sulfonic acids, alkanolamides, ethoxylated fatty alcohols, sorbates and combinations thereof.
[0088] As a further optional component, the starting mixture may include a thickener. In this case, for example, Gel 0625. Further suitable thickeners include polyether urethane solutions, for example Ortegol PV 301 from Evonik Industries. The thickeners ensure in particular stability upon drying.
[0089] The starting mixture may include additional additives, such as stabilizers, including light stabilizers. Solvents may also be added as additional additives. Suitable solvents are those commonly used in the manufacture of polyurethane materials, such as ketones such as acetone, carboxylic acid alkyl esters such as methyl acetate, carbonate alkyl esters or amides such as DMF, or additional liquid flame retardants such as alkyl phosphates such as triethyl phosphate or tributyl phosphate, phosphohalogenated alkyl esters such as tris-(2-chloropropyl) phosphate or tris(1,3-dichloropropyl) phosphate, aryl phosphates such as diphenyltolyl phosphate and phosphonates such as diethyl ethanephosphonate. Also usable are mixtures of the solvents.
[0090] Further optional additives are cell regulators of a type known per se, for example paraffins or fatty alcohols or dimethylpolysiloxanes, flame retardants, pigments or dyes, stabilizers against the effects of ageing and weathering, plasticizers, fungistatic and bacteriostatic substances, fillers, for example barium sulfate, bentonite, kaolin, glass powder, glass beads, glass fibers, calcium carbonate, diatomaceous earth, quartz sand, fluoropolymers, thermoplastics, microbeads, expandable graphite, carbon black or suspended chalk or combinations thereof.
[0091] In a preferred embodiment, expandable microspheres may also be added, which expand when the carrier composition dries. An alternative is the addition of pre-expanded microspheres. Suitable microspheres are described below.
[0092] In the case of the carrier of the invention based on polyurethane produced from dispersion, foaming can be achieved by frothing. The process typically comprises the following steps:
[0093] a) introducing a polyurethane dispersion as described above and at least one surfactant, and optionally further components, such as in particular further dispersions, to form a starting mixture,
[0094] b) mechanically foaming the starting mixture to form a wet polyurethane foam composition, optionally with the addition of further components, such as in particular fillers and / or further additives,
[0095] c) applying the wet polyurethane foam composition to a surface, preferably a temporary support, such as in particular a liner, or a pressure-sensitive adhesive layer,
[0096] d) drying the wet polyurethane foam composition to obtain a polyurethane foam.
[0097] To form polyurethane foam, the starting mixture, i.e. a polyurethane dispersion prepared as above or in some other way, is mechanically beaten (beaten) with at least one surfactant and optionally a solvent and / or further optional ingredients, and foamed. A thickener may optionally be added after the beating has occurred.
[0098] Alternatively, a prepolymer dispersion may be used and the prepolymer polymerized to the polyurethane during a mechanical beating / foaming process.
[0099] A physical blowing agent may be added additionally or alternatively. Thus, for example, the starting mixture may be foamed in the presence of a gas such as air, nitrogen or a noble gas such as helium, neon or argon. The blowing agent may be used alone or as a mixture of different blowing agents. The blowing agent may be selected from a large number of materials, including the following: hydrocarbons, ethers and esters, etc. Typical physical blowing agents have a boiling point in the range of -50°C to +100°C, and preferably -50°C to +50°C. Preferred physical blowing agents include hydrocarbons, such as n-pentane, isopentane and cyclopentane, methylene chloride, or any combination of the above compounds. Such a blowing agent may preferably be used in an amount of 5% to 50% by weight of the reaction mixture, more particularly 10% to 30% by weight of the reaction mixture.
[0100] Chemical blowing agents may also be added in addition or as an alternative. Chemical blowing agents are substances which, only during the processing operation, expel gas due to a chemical reaction (usually initiated by supplying heat) and thereby enable the generation of a foam structure in the polymer. The expelling of gas may be caused by thermal decomposition of the blowing agent or by chemical reactions of various substances present in the blowing agent. The gases formed are usually N2, CO2 or CO.
[0101] The polyurethane-based foamed carrier preferably has a mass of 250 kg / m 3 Up to 500kg / m 3 , more preferably 350 to 450 kg / m 3 density.
[0102] Optionally, a film may be applied over the foam layer. The film, if under tension, may limit the thickness of the foam layer. The film may alternatively only serve as a covering.
[0103] In a further preferred embodiment, before it is brought into or moved into the drying oven, the foam can be applied to a temporary carrier, such as a liner in particular, and / or a pressure-sensitive adhesive layer by a scraper or a blade, so as to achieve a uniform thickness of the foam layer. Alternatively, a roller can also be provided to adjust the thickness of the foam layer.
[0104] The application of the foam layer of the carrier is followed by drying, preferably in a drying oven. Preferred temperatures for drying are 50° C. to 180° C., preferably 50° C. to 120° C., more particularly 70° C. to 115° C., very preferably 100° C. to 115° C. The temperature is preferably at least 50° C., more particularly at least 60° C., more preferably at least 70° C., more particularly at least 80° C., very preferably at least 90° C., more particularly at least 100° C., more particularly at least 110° C., very preferably at least 120° C., more particularly at least 130° C. Furthermore, the temperature is preferably at most 180° C., more particularly at most 170° C., very preferably at most 160° C., more particularly at most 150° C.
[0105] The drying in step d) of the above process sequence is preferably carried out in at least two stages, wherein the drying temperature increases from one step to the next. In contrast to using a high starting temperature (e.g. 120° C.) in the drying process, the staged increase in the drying temperature allows uniform drying, resulting in a uniform distribution of the cell size. At a lower temperature, a relatively uniform initial drying of the entire foam is first carried out, and in a further step, the residual moisture is removed at a higher temperature.
[0106] However, it may also be desirable to achieve a cell size that varies over the cross section. In this case, a high drying temperature should be used from the beginning. This ensures that the foam dries quickly at the surface but remains wet for a long time in the interior, resulting in a different cell size distribution over the cross section.
[0107] The drying in step d) is more preferably carried out in two stages, wherein the drying temperature in the first step is 50 to 100°C, preferably 70 to 90°C, more particularly 80°C, and the drying temperature in the second step is 105 to 180°C, preferably 110 to 150°C, more particularly 120°C.
[0108] The PU-based carrier layer from the dispersion is preferably free of additives, such as antiblocking agents and waxes. For the reasons mentioned above, the polyurethane also preferably has no crystalline superstructure.
[0109] Furthermore, the PU-based carrier layer from the dispersion or the adhesive tape comprising this layer may preferably be subjected to a heat treatment at not less than 150° C. in order to optimize the tensile strength.
[0110] iii) Microspheres
[0111] "Microspheres" are understood to be hollow microspheres with a thermoplastic polymer shell, which are elastic and thus expandable in their ground state. These spheres are filled with low-boiling liquids or liquefied gases. The shell materials used include in particular polyacrylonitrile, PVDC, PVC or polyacrylates. Suitable low-boiling liquids are in particular the following hydrocarbons: lower alkanes, for example isobutane or isopentane, which are encapsulated in the polymer shell as liquefied gas under pressure.
[0112] The action on the microspheres (particularly as a result of heat exposure) causes the outer polymer shell to soften. At the same time, the liquid foaming gas inside the shell changes to its gaseous state. The microspheres undergo an irreversible expansion and three-dimensional expansion at this point. The expansion ends when the internal and external pressures are balanced. Since the polymer shell is retained, the result is a closed-cell foam.
[0113] Various types of microspheres are commercially available and differ essentially in their size, preferably 6 to 45 μm in diameter in the unexpanded state, and in the onset temperature required for their expansion, preferably 75 to 220° C.). An example of commercially available microspheres is DU product (DU=Dry Unexpanded).
[0114] Unexpanded microsphere products are also available in the form of aqueous dispersions with a solid or microsphere fraction of about 40-45% by weight, and additionally, polymer-bound microspheres (masterbatches), for example in ethylene vinyl acetate, at a microsphere concentration of about 65% by weight. Like the DU products, both microsphere dispersions and masterbatches are suitable for making the foamed pressure-sensitive adhesive layer of the present invention.
[0115] The foamed pressure-sensitive adhesives of the invention can also be produced using so-called pre-expanded microspheres. For this group, the expansion takes place even before introduction into the polymer matrix. Pre-expanded microspheres are commercially available, for example, as The name or type designation Expancel xxx DE (dry expanded) comes from Nouryon.
[0116] According to the present invention, the average diameter of the void formed by microspheres in the foamed pressure-sensitive adhesive layer is preferably 10 to 200 μm, more preferably 15 to 200 μm. Since what is measured in this case is the diameter of the void formed by microspheres in the foamed pressure-sensitive adhesive layer, the diameter in question is the diameter of the void formed by the expanded microspheres. Here, average diameter refers to the arithmetic mean of the void diameter formed by microspheres in the pressure-sensitive adhesive layer. The average diameter of the void formed by microspheres in the pressure-sensitive adhesive layer is measured using 5 different freeze-fracture edges of adhesive tape under a scanning electron microscope (SEM) with 500 times magnification. The diameter of the microspheres visible in the microphotograph is graphically determined so that the maximum range (size) of each individual microsphere in the pressure-sensitive adhesive layer under the study in any (two-dimensional) direction is obtained from the SEM microphotograph and is considered to be the diameter of the microsphere.
[0117] In the case of using microspheres for foaming, the microspheres can be supplied to the formulation as a batch (masterbatch), a paste or a blended or unblended powder. They can also be present as a suspension in a solvent.
[0118] The fraction of microspheres in the adhesive according to a preferred embodiment of the invention is between greater than 0% by weight and 10% by weight, more particularly between 0.25% by weight and 5% by weight, very particularly between 0.5 and 1.5% by weight, in each case based on the total composition of the adhesive. These figures refer to unexpanded microspheres.
[0119] The polymer composition of the invention comprising expandable hollow microspheres may additionally comprise non-expandable hollow microspheres. The only critical factor is that substantially all of the gas-containing cavities are closed by a permanently impermeable membrane, whether the membrane consists of a mixture of elastic and thermoplastic stretchable polymers or of elastic glass which is non-thermoplastic in the temperature range possible in plastic processing.
[0120] Additionally suitable (selected independently of the other additives) are solid polymer beads, hollow glass beads, solid glass beads, hollow ceramic beads, solid ceramic beads and / or solid carbon beads (“carbon microspheres”).
[0121] b) Cross-linking agent
[0122] In the present invention, the basis for the carrier is a polyurethane crosslinked with a crosslinking agent. According to common belief, the addition of a crosslinking agent increases the tensile strength level while reducing the maximum stretchability of the polyurethane-based carrier. This would not ensure non-destructive peeling of the adhesive tape. In the present invention, it was surprisingly found that, contrary to common belief, only the breaking force is increased, while the maximum stretchability is hardly changed, with favorable results for the re-peelability of the adhesive tape of the present invention.
[0123] Crosslinkers can react basically in two different ways: by reacting with the polymer, or by reacting with themselves to form a so-called interpenetrating network, which results in a much denser network and thus improves many properties such as strength, abrasion resistance, hydrolysis resistance and chemical resistance.
[0124] Preferred crosslinkers in the context of the present invention are in particular crosslinkers based on aziridine, carbodiimide (polycarbodiimide), melamine, free radical forming substances such as organic peroxides, sulfur and isocyanates. In a preferred embodiment, the crosslinker is an isocyanate, preferably a blocked polyisocyanate, more particularly a blocked aliphatic polyisocyanate.
[0125] Polyisocyanates are capable of reacting with functional groups such as amino or hydroxyl groups. The multifunctionality of this type of crosslinking agent results in a 3D crosslinked network. Polyisocyanates also react with water, which in turn causes the polyisocyanate molecules to react with themselves and produce a network formed by a combination of a conventional 3D polymer crosslinked network and an interpenetrating network brought about by the reactivity of multiple polyisocyanate molecules with themselves.
[0126] In the case of isocyanate crosslinkers, this is preferably obtained from a dispersion comprising a polyisocyanate, a blocking agent for the isocyanate groups and water. In a preferred embodiment, the dispersion used to obtain the crosslinker also comprises a polyamine, preferably a polyamine having at least one carboxyl and / or carboxylate group.
[0127] It is currently considered that polyisocyanates are compounds with NCO groups. Polyisocyanates may have a number average molecular weight of 140 to 1500 g / mol and preferably 168 to 700 g / mol. According to a preferred embodiment of the present invention, polyisocyanates have an isocyanate functionality of>2 and <6, preferably>3 and <5, and more preferably>3 and <4.
[0128] The polyisocyanates preferably have an NCO group content of 15 to 30% by weight, more preferably 18 to 25% by weight and very preferably 20 to 24% by weight, based on the number-average molar mass of the polyisocyanate.
[0129] Suitable polyisocyanates are, for example, hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 4,4'-diisocyanatodicyclohexylmethane (HDI), 12 MDI), 1,4-butane diisocyanate, hexahydrodiisocyanatotoluene, 1,3-bis(isocyanatomethyl)cyclohexane, hexahydrodiisocyanatoxylene, nonane triisocyanate. Particularly preferably, isophorone diisocyanate, hexamethylene diisocyanate and / or 4,4'-diisocyanatodicyclohexylmethane are used.
[0130] Particularly preferred polyisocyanates used are aliphatic polyisocyanates, preferably hexamethylene diisocyanate and more preferably trimers of hexamethylene diisocyanate. It is also advantageous if the aqueous blocked polyurethane urea dispersion is only anionically hydrophilized. This means that the polyurethane urea dispersion is not cationic and / or nonionic hydrophilized, i.e., has no corresponding groups.
[0131] Blocking agents are now understood to mean compounds which are capable of reacting with isocyanate groups and which can be eliminated from the isocyanate groups again under defined conditions (e.g. thermally). This process is known as deblocking. Low deblocking temperatures have proven to be particularly advantageous within the scope of the present invention. Therefore, in a preferred embodiment, the deblocking temperature is below 130° C.
[0132] Examples of suitable isocyanate-based crosslinkers which have proven suitable are those obtainable under the trade name Iprafix 2794 from Covestro, Germany.
[0133] Polycarbodiimides react selectively with carboxylic acid groups in polymer chains. This type of crosslinking produces a conventional 3D polymer crosslinked network. Compared to polyisocyanates, polycarbodiimides are less sensitive to water and therefore achieve a longer pot life.
[0134] Due to their high reactivity, melamine resins are very effective crosslinkers. They require lower addition levels compared to isocyanates or carbodiimides. Melamine resins are often used in combination with hydroxy-functional polymer resins, which form very rigid networks but are also able to react with acid groups. Melamine resins require very high crosslinking temperatures, which can be lowered by adding catalysts.
[0135] Polyethylenimine is sometimes the most reactive crosslinking agent and is therefore highly efficient. Polyethylenimine reacts selectively with carboxylic acid groups in polymer chains. This type of crosslinking produces a conventional 3D polymer crosslinked network. Due to the lower molecular weight, substantially lower fractions are required compared to polyisocyanates and polycarbodiimides.
[0136] Peroxide crosslinking results in a high degree of crosslinking, as well as favorable processing and a wide range of applicability. However, the vulcanization time is very long.
[0137] For crosslinking with sulfur, a vulcanization accelerator must usually be added to prevent degradation phenomena at the temperatures used for crosslinking. The elasticity and low-temperature strength of the vulcanized product (vulcanizate) are usually low.
[0138] c) Pressure sensitive adhesive
[0139] For adhesive tapes that can be peeled off again without residue or destruction by stretching in the bonding plane, they need to have specific adhesive properties. Therefore, when stretched, there must be a significant decrease in the viscosity of the adhesive tape. The lower the adhesive performance under tension, the less significant the damage to the substrate when peeling, or the less significant the risk of residues being left on the adhesive substrate. In this regard, it has been proven that particularly advantageous pressure-sensitive adhesives are those based on vinyl aromatic block copolymers, more particularly styrene block copolymers, as used in the present invention.
[0140] The vinyl aromatic block copolymer is preferably at least one having AB, ABA, (AB) n , (AB) n X or (ABA) n A synthetic rubber in the form of a block copolymer of structure X, wherein
[0141] - the A blocks are independently of one another polymers formed by polymerization of vinyl aromatic compounds;
[0142] - the B blocks are independently of one another polymers formed by polymerization of conjugated dienes having 4 to 18 carbon atoms and / or isobutylene, or partially or fully hydrogenated derivatives of such polymers;
[0143] -X is a group (residue) of a coupling agent or an initiator; and
[0144] -n is an integer ≥ 2.
[0145] More preferably, all synthetic rubbers of the pressure-sensitive adhesive according to the present invention are block copolymers having the structure as described above. Therefore, the pressure-sensitive adhesive according to the present invention may also include a mixture of a plurality of block copolymers having the structure as described above.
[0146] Suitable block copolymers include one or more rubbery (rubbery) blocks B (soft blocks) and one or more glassy (glassy) blocks A (hard blocks). More preferably, at least one synthetic rubber of the pressure-sensitive adhesive according to the present invention is a block copolymer having an AB, ABA, (AB) 3X or (AB) 4X structure, wherein the above meaning is applicable to A, B and X, and wherein at least one block copolymer comprises at least two hard blocks. Most preferably, all synthetic rubbers in the pressure-sensitive adhesive according to the present invention are block copolymers having an AB, ABA, (AB) 3X or (AB) 4X structure, wherein the above meaning is applicable to A, B and X. More particularly, the synthetic rubber in the pressure-sensitive adhesive according to the present invention is a mixture of block copolymers having an AB, ABA, (AB) 3X or (AB) 4X structure, which preferably includes at least a diblock copolymer AB and / or a triblock copolymer ABA.
[0147] Also advantageous are diblock and triblock copolymers and (AB) wherein n is not less than 3. n or (AB) n X is a mixture of block copolymers.
[0148] The block copolymers produced by the A and B blocks may contain the same or different B blocks. The block copolymers may have a linear ABA structure. Block copolymers in radial form as well as star-shaped and linear multiblock copolymers may also be used. The additional component present may be an AB diblock copolymer. The above polymers may be used individually or in mixtures with one another, although the AB diblock copolymers are not usable individually.
[0149] The A block is in particular a glassy block having a preferred glass transition temperature (Tg, DSC) above room temperature. More preferably, the Tg of the glassy block is at least 40° C., in particular at least 60° C., very preferably at least 80° C., and most preferably at least 100° C. The proportion of vinyl aromatic blocks A in the overall mass of the block copolymer is preferably 10 to 40% by weight, more preferably 20 to 33% by weight. The vinyl aromatic compounds used to form the A block preferably include styrene and α-methylstyrene. The A block can therefore be in the form of a homopolymer or a copolymer. More preferably, the A block is polystyrene.
[0150] The B block is especially a rubbery block or soft block having a preferred Tg below room temperature. More preferably, the soft block has a Tg of less than 0°C, especially less than -10°C, for example less than -40°C and very preferably less than -60°C.
[0151] The monomer units used to form the A block preferably include styrene, α-methylstyrene and / or other styrene derivatives. The A block may thus be in the form of a homopolymer or a copolymer. More preferably, the A block is polystyrene.
[0152] Preferred conjugated dienes as monomers for the soft block B are in particular selected from butadiene, isoprene, ethylbutadiene, phenylbutadiene, piperylene, pentadiene, hexadiene, ethylhexadiene and dimethylbutadiene, and any desired mixtures of these monomers. The B block may also be in the form of a homopolymer or a copolymer. More preferably, the conjugated diene as monomer for the soft block B is selected from butadiene and isoprene. For example, the soft block B is polyisoprene, polybutadiene, or a partially or completely hydrogenated derivative of one of these two polymers, such as in particular polybutene-butadiene, or a polymer formed from a mixture of butadiene and isoprene. Most preferably, the B block is polybutadiene.
[0153] The A blocks are also referred to as "hard blocks" within the scope of the present invention. The B blocks are also referred to as "soft blocks" or "elastomeric blocks" accordingly. This reflects the selection of the blocks according to the invention according to their glass transition temperature: preferably, for the A blocks, at least 25° C., in particular at least 50° C., and for the B blocks, at most 25° C., in particular at most −25° C.
[0154] In a preferred configuration, the total proportion of vinyl aromatic block copolymers is 15 to 60% by weight, more preferably 20 to 50% by weight, based on the total pressure-sensitive adhesive. Too low a proportion of vinyl aromatic block copolymers has the following result: the cohesion of the pressure-sensitive adhesive is relatively low, and the tear strength required for peeling is therefore too low. Too high a proportion of vinyl aromatic block copolymers again leads to almost no pressure-sensitive adhesion in the pressure-sensitive adhesive.
[0155] The pressure-sensitive adhesive according to the present invention is based on a vinyl aromatic block copolymer, which is preferably mixed with a tackifier resin that is miscible with an elastomer. In addition to at least one vinyl aromatic block copolymer, the pressure-sensitive adhesive preferably includes at least one tackifier resin to improve adhesion in a desired manner. The tackifier should be compatible with the elastomer block of the block copolymer.
[0156] According to the general understanding of those skilled in the art, "tackifier resin" is understood to mean an oligomeric or polymeric resin which increases the adhesion (tack, inherent tack) of a pressure-sensitive adhesive compared to an otherwise identical pressure-sensitive adhesive that does not contain any tackifier resin.
[0157] In a preferred embodiment, the adhesive layer consists of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer and a tackifier resin, wherein the tackifier resin is selected to an extent of at least 30% by weight and preferably to an extent of at least 50% by weight (in each case based on the total tackifier resin content) to have a DACP (diacetone alcohol cloud point) of more than -20°C, preferably more than 0°C and a softening temperature (ring and ball method) of not less than 70°C, preferably not less than 100°C.
[0158] More preferably, the tackifier resin comprises at least 30% by weight, such as in particular at least 50% by weight, of hydrocarbon resin or terpene resin or mixtures thereof, in each case based on the total tackifier resin content.
[0159] It has been found that tackifier resins that can be advantageously used for pressure-sensitive adhesives are in particular non-polar hydrocarbon resins such as hydrogenated and non-hydrogenated polymers of dicyclopentadiene, hydrocarbon resins that are not hydrogenated, partially, selectively or fully hydrogenated based on C5, C5 / C9 or C9 monomer streams (logistics), and polyterpene resins based on α-pinene and / or β-pinene and / or δ-limonene. The above tackifier resins can be used alone or in a mixture. Room temperature solid resins or liquid resins can be used. Tackifier resins (which also contain oxygen) in hydrogenated or non-hydrogenated form can be optionally and preferably used in adhesives in a maximum proportion of up to 70% by weight, based on the total mass of the resin.
[0160] In a preferred variant, the proportion of resins which are liquid at room temperature is up to 15% by weight, preferably up to 10% by weight, based on the total pressure-sensitive adhesive.
[0161] The pressure-sensitive adhesive according to the invention preferably comprises 20 to 60 wt% of at least one tackifier resin, based on the total weight of the pressure-sensitive adhesive. More preferably, the tackifier resin is present to an extent of 30 to 50 wt%, based on the total weight of the pressure-sensitive adhesive.
[0162] Further additives that may typically be used are:
[0163] - plasticizers, for example plasticizer oils, or low molecular weight liquid polymers such as low molecular weight polybutenes, preferably in a proportion of 0.2 to 5% by weight, based on the total weight of the pressure-sensitive adhesive
[0164] - a primary antioxidant, such as a hindered phenol, preferably in a proportion of 0.2 to 1% by weight, based on the total weight of the pressure-sensitive adhesive
[0165] - secondary antioxidants, such as phosphites or thioethers, preferably in a proportion of 0.2 to 1% by weight, based on the total weight of the pressure-sensitive adhesive
[0166] - Processing stabilizers, for example C free radical scavengers, preferably in a proportion of 0.2 to 1% by weight, based on the total weight of the pressure-sensitive adhesive
[0167] - Light stabilizers, such as UV absorbers or hindered amines, preferably in a proportion of 0.2 to 1% by weight, based on the total weight of the pressure-sensitive adhesive
[0168] - processing aids, preferably in a proportion of 0.2 to 1% by weight, based on the total weight of the pressure-sensitive adhesive
[0169] - an end-block reinforcing resin, preferably in a proportion of 0.2 to 10% by weight, based on the total weight of the pressure-sensitive adhesive, and
[0170] - Optionally, further polymers, which are preferably of elastomeric nature; elastomers which can be used accordingly include in particular those based on pure hydrocarbons, for example unsaturated polydienes such as naturally or synthetically produced polyisoprene or polybutadiene, essentially chemically saturated elastomers, for example saturated ethylene-propylene copolymers, α-olefin copolymers, polyisobutylene, butyl rubber, ethylene-propylene rubber, and chemically functionalized hydrocarbons, for example halogenated, acrylated, allyl-containing or vinyl ether-containing polyolefins; preferably in a proportion of 0.2 to 10% by weight, based on the total weight of the pressure-sensitive adhesive.
[0171] The nature and amounts of the blending components can be selected as desired.
[0172] It is also in accordance with the invention if the adhesive does not comprise some, preferably any, of the respective additives mentioned.
[0173] In one embodiment of the invention, the pressure-sensitive adhesive further comprises additional additives; non-limiting examples include crystalline or amorphous oxides, hydroxides, carbonates, nitrides, halides, carbides, or mixed oxide / hydroxide / halide compounds of aluminum, silicon, zirconium, titanium, tin, zinc, iron or alkali / alkaline earth metals. These are essentially alumina such as aluminum oxide, boehmite, bayerite, gibbsite, diaspore, etc. Layered silicates are very particularly suitable, such as bentonite, montmorillonite, hydrotalcite, hectorite, kaolinite, boehmite, mica, vermiculite or mixtures thereof. However, other polymorphs of carbon black or carbon such as carbon nanotubes may also be used.
[0174] The adhesive can also be colored with dyes or pigments. The adhesive can be white, black or colored, and transparent.
[0175] The plasticizer introduced by metered addition may be, for example, a (meth)acrylate oligomer, a phthalate, a cyclohexanedicarboxylate, a water-soluble plasticizer, a plasticizing resin, a phosphoric acid ester or a polyphosphate.
[0176] Addition of silica, advantageously precipitated silica surface-modified with dimethyldichlorosilane, can be used to adjust the hot shear strength of the pressure-sensitive adhesive.
[0177] In a preferred embodiment, the pressure sensitive adhesive of the present invention is already foamed. As mentioned above, foaming is typically accomplished by the introduction and subsequent expansion of microspheres.
[0178] The absolute density of the foamed pressure-sensitive adhesive according to the present invention is preferably 220-990 kg / m 3 , more preferably 300-970kg / m 3 , even more preferably 450-900kg / m 3 , especially 500-850kg / m3 The relative density describes the density of the foamed pressure-sensitive adhesive according to the invention in relation to the density of the unfoamed pressure-sensitive adhesive according to the invention with the same formulation. The relative density of the pressure-sensitive adhesive according to the invention is preferably 0.20-0.99, more preferably 0.30-0.97, in particular 0.45-0.90, for example 0.50-0.85.
[0179] In a preferred embodiment of the present invention, the adhesive consists only of the vinyl aromatic block copolymer, the optional tackifier resin, the microspheres and the optional additives mentioned above.
[0180] Further preferably, the pressure-sensitive adhesive consists of the following components:
[0181] - Styrene block copolymer 20 to 75 wt%
[0182] - Tackifier resin 24.6 wt% to 60 wt%
[0183] - Microspheres 0.2% to 10% by weight
[0184] - Additives 0.2 wt% to 10 wt%
[0185] Further preferably, the adhesive consists of the following components:
[0186] - Styrene block copolymer 35 to 65 wt%
[0187] - Tackifier resin 34.6 wt% to 45 wt%
[0188] - Microspheres 0.2% to 10% by weight
[0189] - Additives 0.2 wt% to 10 wt%
[0190] Pressure-sensitive adhesives which have proven to be particularly suitable in this respect are styrene block copolymers, more particularly styrene-butadiene block copolymers. Thus, in a preferred embodiment, the styrene block copolymer forming the basis for the pressure-sensitive adhesive comprises a styrene-butadiene block copolymer.
[0191] The pressure-sensitive adhesive layer of the adhesive tape of the invention is preferably based on a vinyl aromatic block copolymer or a blend of a vinyl aromatic block copolymer and a polyacrylate, wherein the vinyl aromatic block copolymer is preferably substantially immiscible with the polyacrylate. Such a blend preferably consists of 50 to 90 wt. %, preferably 65 to 80 wt. %, of polyacrylate and 10 to 50 wt. %, preferably 20 to 35 wt. %, of the vinyl aromatic block copolymer adhesive, wherein the two weight fractions add up to 100 wt. %.
[0192] A pressure-sensitive adhesive (PSA) based on a polymer or polymer mixture (i.e. based on a polymer blend) is understood within the scope of the present patent application to mean, in particular, that the polymer or polymer mixture accounts for at least 50% by weight, preferably at least 90% by weight, of all polymer components in the PSA. In a particularly preferred embodiment, the polymer or polymer mixture constitutes the only polymer in the adhesive. Any tackifier resin present in the adhesive is not considered a polymer in this case.
[0193] "Poly(meth)acrylates" are polymers obtainable by free-radical polymerization of acrylic and / or methacrylic monomers, and optionally further copolymerizable monomers. More particularly, "poly(meth)acrylates" are polymers whose monomer base consists to an extent of at least 50% by weight of acrylic acid, methacrylic acid, acrylic acid esters and / or methacrylic acid esters, wherein acrylic acid esters and / or methacrylic acid esters are at least partially, preferably to an extent of at least 30% by weight, based on the total monomer base of the polymer in question.
[0194] The pressure-sensitive adhesive of the invention comprises poly(meth)acrylates, preferably in total 35-65% by weight, more preferably in total 40-60% by weight, in each case based on the total weight of the pressure-sensitive adhesive. One (single) poly(meth)acrylate or a plurality of poly(meth)acrylates may be present.
[0195] The glass transition temperature of the poly(meth)acrylate of the pressure-sensitive adhesive of the present invention is preferably <0°C, more preferably between -20 and -50°C.
[0196] The poly(meth)acrylate of the pressure-sensitive adhesive of the present invention preferably comprises at least one partially copolymerized functional monomer, more preferably a monomer that is reactive with epoxy groups to form covalent bonds. Very preferably, the partially copolymerized functional monomer, more preferably a monomer that is reactive with epoxy groups to form covalent bonds, comprises at least one functional group selected from the group consisting of carboxylic acid groups, sulfonic acid groups, phosphonic acid groups, hydroxyl groups, anhydride groups, epoxy groups and amino groups; more particularly, it comprises at least one carboxylic acid group. Very preferably, the poly(meth)acrylate of the pressure-sensitive adhesive of the present invention comprises partially copolymerized acrylic acid and / or methacrylic acid. All stated groups have reactivity with epoxy groups, thus making the poly(meth)acrylate advantageously suitable for thermal crosslinking with introduced epoxides.
[0197] The poly(meth)acrylate of the pressure-sensitive adhesive of the present invention may preferably be derived from the following monomer composition:
[0198] a) at least one acrylate and / or methacrylate of the following formula (1):
[0199] CH2=C(RI )(COOR II ) (1),
[0200] Where R I is H or CH3 and R II is an alkyl group having 4 to 18 carbon atoms,
[0201] b) at least one ethylenically unsaturated monomer having at least one functional group selected from the group consisting of a carboxylic acid group, a sulfonic acid group, a phosphonic acid group, a hydroxyl group, an acid anhydride group, an epoxy group and an amino group;
[0202] c) Optionally, further acrylates and / or methacrylates and / or ethylenically unsaturated monomers copolymerizable with component (a).
[0203] It is particularly advantageous to select monomers of component a) with a fraction of 45-99% by weight, monomers of component b) with a fraction of 1-15% by weight and monomers of component c) with a fraction of 0-40% by weight, the figures being based on the monomer mixture for the base polymer without addition of possible additives such as resins etc.
[0204] The monomers of component a) are generally plasticizing, relatively non-polar monomers. More preferably, R II is an alkyl group having 4 to 10 carbon atoms or 2-propylheptyl acrylate or 2-propylheptyl methacrylate. The monomer of formula (1) is more particularly selected from n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-pentyl methacrylate, n-pentyl acrylate, n-hexyl acrylate, n-hexyl methacrylate, n-heptyl acrylate, n-octyl acrylate, n-octyl methacrylate, n-nonyl acrylate, isobutyl acrylate, isooctyl acrylate, isooctyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-propylheptyl acrylate and 2-propylheptyl methacrylate.
[0205] The monomers of component b) are more preferably selected from acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, aconitic acid, dimethacrylic acid, β-acryloxypropionic acid, trichloroacrylic acid, vinylacetic acid, vinylphosphonic acid, maleic anhydride, hydroxyethyl acrylate, in particular 2-hydroxyethyl acrylate, hydroxypropyl acrylate, in particular 3-hydroxypropyl acrylate, hydroxybutyl acrylate, in particular 4-hydroxybutyl acrylate, hydroxyhexyl acrylate, in particular 6-hydroxyhexyl acrylate, hydroxyethyl methacrylate, in particular 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, in particular 3-hydroxypropyl methacrylate, hydroxybutyl methacrylate, in particular 4-hydroxybutyl methacrylate, hydroxyhexyl methacrylate, in particular 6-hydroxyhexyl methacrylate, allyl alcohol, glycidyl acrylate, glycidyl methacrylate.
[0206] Illustrative monomers of component c) are:
[0207] Methyl acrylate, ethyl acrylate, propyl acrylate, methyl methacrylate, ethyl methacrylate, benzyl acrylate, benzyl methacrylate, sec-butyl acrylate, tert-butyl acrylate, phenyl acrylate, phenyl methacrylate, isobornyl acrylate, isobornyl methacrylate, tert-butylphenyl acrylate, tert-butylphenyl methacrylate, dodecyl methacrylate, isodecyl acrylate, lauryl acrylate, n-undecyl acrylate, stearyl acrylate, tridecyl acrylate, behenyl acrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, 2-butoxyethyl methacrylate, 2-butoxyethyl acrylate, 3,3,5-trimethylol acrylate Cyclohexyl acrylate, 3,5-dimethyladamantyl acrylate, 4-cumylphenyl methacrylate, cyanoethyl acrylate, cyanoethyl methacrylate, 4-biphenyl acrylate, 4-biphenyl methacrylate, 2-naphthyl acrylate, 2-naphthyl methacrylate, tetrahydrofurfuryl acrylate, diethylaminoethyl acrylate, diethylaminoethyl methacrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, methyl 3-methoxyacrylate, 3-methoxybutyl acrylate, 2-phenoxyethyl methacrylate, butyl diglycol methacrylate, ethylene glycol acrylate, ethylene glycol monomethacrylate (ethylene glycol monomethyl ether acrylate), methoxy polyethylene glycol methacrylate 350, methoxy polyethylene glycol methacrylate Acid 500, propylene glycol monomethacrylate, butoxydiglycol methacrylate, ethoxytriglycol methacrylate, octafluoropentyl acrylate, octafluoropentyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorobutyl acrylate, 2,2,3,3,4,4,4-heptafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorooctyl methacrylate, dimethylaminopropyl acrylamide, dimethylaminopropyl methacrylamide, N-(1-methylundecyl)acrylamide, N-(n-butoxymethyl)acrylamide, N-(butoxymethyl)methacrylamide, N-(ethoxymethyl)acrylamide, N-(n-octadecyl)acrylamide; N,N-dialkyl substituted amides such as N,N-dimethylacrylamide and N,N-dimethylmethacrylamide; N-benzyl acrylamide, N-isopropyl acrylamide, N-tert-butyl acrylamide, N-tert-octylacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, acrylonitrile, methacrylonitrile; vinyl ethers such as vinyl methyl ether, ethyl vinyl ether, vinyl isobutyl ether; vinyl esters such as vinyl acetate;Vinyl halides, vinylidene (vinylidene) halides, vinyl pyridine, 4-vinyl pyridine, N-vinyl phthalimide, N-vinyl lactam, N-vinyl pyrrolidone, styrene, α-methyl styrene and p-methyl styrene, α-butyl styrene, 4-n-butyl styrene, 4-n-decyl styrene, 3,4-dimethoxy styrene; macromonomers such as 2-polystyrene ethyl methacrylate (weight average molecular weight Mw of 4000-13000 g / mol, determined by GPC), poly (methyl methacrylate) ethyl methacrylate (Mw of 2000-8000 g / mol). ;
[0208] The monomers of component c) can also advantageously be selected so that they contain functional groups which support subsequent radiation-chemical crosslinking (for example by electron beam or UV radiation). Suitable copolymerizable photoinitiators are, for example, benzoin acrylates and acrylate-functionalized benzophenone derivatives. Monomers which support crosslinking by electron beam bombardment are, for example, tetrahydrofurfuryl acrylate, N-tert-butylacrylamide and allyl acrylate.
[0209] The poly(meth)acrylates are preferably prepared by conventional free radical polymerization or controlled free radical polymerization. The poly(meth)acrylates can be prepared by copolymerizing the monomers using conventional polymerization initiators and optionally chain transfer agents, wherein the polymerization is carried out at conventional temperatures in bulk (in bulk), in emulsion (for example in water or liquid hydrocarbons) or in solution.
[0210] The poly(meth)acrylates are preferably prepared by copolymerizing the monomers in a solvent, more preferably in a solvent having a boiling range of 50 to 150° C., more particularly 60 to 120° C., using 0.01 to 5% by weight of polymerization initiator, more particularly 0.1 to 2% by weight of polymerization initiator, in each case based on the total weight of the monomers.
[0211] All customary initiators are suitable in principle. Examples of free radical sources are peroxides, hydroperoxides and azo compounds, such as dibenzoyl peroxide, cumene hydroperoxide, cyclohexanone peroxide, di-tert-butyl peroxide, cyclohexylsulfonylacetyl peroxide, diisopropyl percarbonate, tert-butyl peroctoate and benzopinacol. A preferred free radical initiator is 2,2'-azobis(2-methylbutyronitrile) (from DuPont 67 TM ) or 2,2'-azobis(2-methylpropionitrile) (2,2'-azobisisobutyronitrile; AIBN; from DuPont 64 TM ).
[0212] Preferred solvents for preparing poly(meth)acrylates are alcohols such as methanol, ethanol, n-propanol and isopropanol, n-butanol and isobutanol, in particular isopropanol and / or isobutanol; hydrocarbons such as toluene and in particular mineral spirits (mineral spirits) having a boiling range of 60-120° C.; ketones, in particular acetone, methyl ethyl ketone, methyl isobutyl ketone; esters such as ethyl acetate; and mixtures of the abovementioned solvents. Particularly preferred solvents are mixtures which comprise isopropanol in an amount of 2-15% by weight, more particularly 3-10% by weight, in each case based on the solvent mixture used.
[0213] Preferably, after the preparation of the poly(meth)acrylate (polymerization), there is a concentration process and the further processing of the poly(meth)acrylate is essentially solvent-free. The concentration of the polymer can be carried out in the absence of crosslinking agents and promoter substances. However, it is also possible to add one of these types of compounds to the polymer even before the concentration, in which case the concentration is carried out in the presence of said substances.
[0214] The polymer after the concentration step can be transferred to a compounder. Concentration and compounding can also optionally be carried out in the same reactor.
[0215] The weight average molecular weight Mw of the polyacrylates is preferably from 20 000 to 2 000 000 g / mol, very preferably from 100 000 to 1 500 000 g / mol, most preferably from 150 000 to 1 000 000 g / mol. For this purpose, it may be advantageous to carry out the polymerization in the presence of suitable chain transfer agents such as mercaptans, halogen compounds and / or alcohols to establish the desired average molecular weight.
[0216] The figures for the number-average molecular weight Mn and the weight-average molecular weight Mw herein are based on the determination known per se by gel permeation chromatography (GPC). The determination is carried out on 100 μl of a sample (sample concentration 4 g / l) which has undergone a clarifying filtration. The eluent used is tetrahydrofuran with 0.1% by volume of trifluoroacetic acid. The measurements are carried out at 25° C.
[0217] The pre-column used was a PSS-SDV column, 5 μm, 8.0mm*50mm (Details here and below are in the following order: type, particle size, porosity, inner diameter*length; ). The following combination was used for separation: PSS-SDV column, 5 μm, as well as and Each has 8.0 mm*300 mm (column from Polymer Standards Service; detection using Shodex RI71 differential refractometer). The flow rate is 1.0 ml / min. In the case of poly(meth)acrylates, the PMMA standard is calibrated (polymethyl methacrylate calibration), and in the other cases (resin, elastomer) the PS standard is calibrated (polystyrene calibration).
[0218] The poly(meth)acrylates preferably have a K value, measured in toluene (1% strength solution, 21° C.), of 30 to 90, more preferably 40 to 70. The K value according to Fikentscher is a measure of the molecular weight and viscosity of the polymer.
[0219] The principle of this method is based on the determination of relative solution viscosity by capillary viscometry. To this end, the substance to be tested is dissolved in toluene by shaking for 30 minutes to obtain a 1% concentration solution. The flow time from the Vogel-Ossag viscometer is measured at 25°C, and the relative viscosity of the sample solution is determined from this, relative to the viscosity of the pure solvent. The K value can be read from the table by the method of Fikentscher [PE Hinkamp, Polymer, 1967, 8, 381] (K = 1000k).
[0220] The poly (meth) acrylate of the PSA of the present invention may preferably have a polydispersity of PD <4 and thus a relatively narrow molecular weight distribution. Despite the relatively low molecular weight, the composition based thereon has particularly good shear strength after the crosslinking step. Moreover, the lower polydispersity enables easier processing from the melt because the fluid viscosity is lower than that of a wider distributed poly (meth) acrylate having substantially the same performance properties. Narrowly distributed poly (meth) acrylates may advantageously be prepared by anionic polymerization or by controlled radical polymerization techniques, the latter being particularly suitable. Such poly (meth) acrylates may also be prepared via N-oxyl groups. In addition, in an advantageous manner, atom transfer radical polymerization (ATRP) may be used to synthesize narrowly distributed poly (meth) acrylates, in which case the initiator used preferably comprises a monofunctional or difunctional secondary or tertiary halide, wherein the extraction of the halide is implemented using a complex of Cu, Ni, Fe, Pd, Pt, Ru, Os, Rh, Co, Ir, Ag or Au. RAFT polymerization is also suitable.
[0221] The poly(meth)acrylates of the PSA of the invention are preferably crosslinked by a bonding reaction of the functional groups they contain with a thermal crosslinker, in particular in the sense of an addition or substitution reaction. All thermal crosslinkers can be used:
[0222] - both to ensure a sufficiently long working (processing) time so that there is no gelling during processing operations, especially during the extrusion process,
[0223] - This in turn leads to rapid postcrosslinking of the polymer to the desired degree of crosslinking at temperatures below the processing temperature, more particularly at room temperature.
[0224] For example, possible are combinations of polymers containing carboxyl groups, amino groups and / or hydroxyl groups with isocyanates, in particular aliphatic or blocked isocyanates (examples are trimeric isocyanates deactivated with amines) as crosslinkers. Suitable isocyanates are in particular trimer derivatives of MDI [4,4-methylenedi(phenylisocyanate)], HDI [hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate] and IPDI [isophorone diisocyanate, 5-isocyanato-1-isocyanatomethyl-1,3,3-trimethylcyclohexane].
[0225] Preference is given to using from 0.1 to 5% by weight, more particularly from 0.2 to 1% by weight, of thermal crosslinkers, based on the total amount of polymer to be crosslinked.
[0226] Also possible is crosslinking via complexing agents (also called chelates). An example of a preferred complexing agent is aluminum acetylacetonate.
[0227] The poly(meth)acrylates of the PSA of the invention are preferably crosslinked via one or more epoxides or substances containing epoxy groups. Substances containing epoxy groups are in particular polyfunctional epoxides, these being those having at least two epoxy groups; thus, there is generally an indirect linking of the components of the poly(meth)acrylates carrying the functional groups. Substances containing epoxy groups may be aromatic and aliphatic compounds.
[0228] Very suitable polyfunctional epoxides are oligomers of epichlorohydrin, epoxy ethers of polyols, especially ethylene glycol, propylene glycol and butanediol, polyethylene glycol, thiodiglycol, glycerol, pentaerythritol, sorbitol, polyvinyl alcohol, polyallyl alcohol, etc.; polyphenols, more particularly resorcinol, hydroquinone, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3-methylphenyl)methane, bis(4-hydroxy-3,5-dibromophenyl)methane, bis(4-hydroxy-3,5-difluorophenyl)methane, 1-[ ... , 1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, bis(4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl) 1,1-bis(4-hydroxyphenyl)-2,2,2-trichloroethane, bis(4-hydroxyphenyl)-(4-chlorophenyl)methane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)cyclohexylmethane, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl sulfone and the epoxy ethers thereof; phenol-formaldehyde condensation products such as phenol alcohols and phenolic resins; S-containing epoxides and N-containing epoxides epoxides prepared by conventional methods from monounsaturated carboxylic acid esters of unsaturated alcohols or polyunsaturated carboxylic acids; glycidyl esters; polyglycidyl esters which can be obtained by polymerization or copolymerization of glycidyl esters of unsaturated acids or can be obtained from other acidic compounds such as cyanuric acid, diglycidyl sulfide or cyclic trimethylene trisulfone and / or derivatives of these.
[0229] Examples of very suitable ethers are 1,4-butanediol diglycidyl ether, polyglycerol-3-glycidyl ether, cyclohexanedimethanol diglycidyl ether, glycerol triglycidyl ether, neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, bisphenol A diglycidyl ether and bisphenol F diglycidyl ether.
[0230] Further preferred epoxides are cycloaliphatic epoxides, for example 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (UVACure 1500).
[0231] The poly(meth)acrylates are more preferably crosslinked using a crosslinker-accelerator system ("crosslinking system"), in order to achieve more effective control over the processing time, the crosslinking kinetics and the degree of crosslinking. The crosslinker-accelerator system preferably comprises at least one substance containing epoxy groups as crosslinker and at least one substance as accelerator which has an accelerating effect on the crosslinking reaction by means of a compound containing epoxy groups at a temperature below the melting temperature of the polymer to be crosslinked.
[0232] The accelerators used in the invention are particularly preferably amines. These are formally explained as substitution products of amino; in the formulae that follow, the substituents are represented by "R" and include in particular alkyl and / or aryl groups. Particular preference is given to using amines which undergo no reaction or only little reaction with the units of the polymer to be crosslinked.
[0233] The selectable accelerators include in principle primary amines (NRH2), secondary amines (NR2H) or tertiary amines (NR3), which of course include those with two or more primary and / or secondary and / or tertiary amino groups. Particularly preferred accelerators are tertiary amines, such as triethylamine, triethylenediamine, benzyldimethylamine, dimethylaminomethylphenol, 2,4,6-tris(N,N-dimethylaminomethyl)phenol, N,N'-bis(3-(dimethylamino)propyl)urea. Further preferred accelerators are polyfunctional amines such as diamines, triamines and / or tetraamines, for example diethylenetriamine, triethylenetetramine, trimethylhexamethylenediamine.
[0234] Other preferred accelerators are amino alcohols, especially secondary and / or tertiary amino alcohols, and if there are two or more amino functions per molecule, preferably at least one and more preferably all of the amino functions are secondary and / or tertiary. Particularly preferred such accelerators are triethanolamine, N,N-bis(2-hydroxypropyl)ethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, 2-aminocyclohexanol, bis(2-hydroxycyclohexyl)methylamine, 2-(diisopropylamino)ethanol, 2-(dibutylamino)ethanol, N-butyldiethanolamine, N-butylethanolamine, 2-[bis(2-hydroxyethyl)amino]-2-(hydroxymethyl)-1,3-propanediol, 1-[bis(2-hydroxyethyl)amino]-2-propanol, triisopropanolamine, 2-(dimethylamino)ethanol, 2-(diethylamino)ethanol, 2-(2-dimethylaminoethoxy)ethanol, N,N,N'-trimethyl-N'-hydroxyethylbisaminoethyl ether, N,N,N'-trimethylaminoethylethanolamine and N,N,N'-trimethylaminopropylethanolamine.
[0235] Further suitable accelerators are pyridine, imidazoles such as 2-methylimidazole, and 1,8-diazabicyclo[5.4.0]undec-7-ene. Alicyclic polyamines can also be used as accelerators. Other suitable phosphorus-based accelerators are phosphine and / or Compounds such as triphenylphosphine or tetraphenylphosphine Tetraphenylborate.
[0236] Quaternary ammonium compounds may also be used as accelerators; examples are tetrabutylammonium hydroxide, cetyltrimethylammonium bromide, and benzalkonium chloride.
[0237] As is usually always the case in such PSAs, preferably the poly(meth)acrylate and the synthetic rubber are each respectively present as a homogeneous phase in the PSA of the invention. More preferably, the synthetic rubber is dispersed in the poly(meth)acrylate.
[0238] Thus, preferably, the poly(meth)acrylate and the synthetic rubber present in the PSA are immiscible with each other to homogeneity at 23° C. Thus, the PSA of the present invention preferably has at least two-phase morphology at least microscopically (under a microscope) and at least at room temperature. More preferably, the poly(meth)acrylate and the synthetic rubber are inhomogeneously miscible with each other in the temperature range of -20° C. to 90° C., more particularly 0° C. to 60° C., and thus in these temperature ranges, the PSA is present as at least two phases at least microscopically.
[0239] In the sense of the present specification, components are defined as "inhomogeneously miscible with each other" when, even after intimate mixing, the formation of at least two stable phases (physically and / or chemically) is at least microscopically detectable, wherein one phase is enriched in one component and the second phase is enriched in the other component. The presence of negligible small amounts of one component in the other component does not violate the formation of a multiphase system and is considered irrelevant (unimportant). Thus, small amounts of synthetic rubber may be present in the poly(meth)acrylate phase and / or small amounts of poly(meth)acrylate components may be present in the synthetic rubber phase, these being not significant amounts that affect phase separation.
[0240] In particular, the phase separation can be achieved such that discrete regions ("domains") rich in synthetic rubber (in other words essentially formed by synthetic rubber) are present in a continuous matrix rich in poly(meth)acrylate (in other words essentially formed by poly(meth)acrylate). For example, a suitable analytical system for the phase separation is scanning electron microscopy. Alternatively, the phase separation can also be detectable, for example, by different phases having two glass transition temperatures that are independent of each other in dynamic scanning calorimetry (DSC) or dynamic mechanical analysis (DMA). In particular, the phase separation is present according to the invention when it can be clearly shown by at least one of the analytical methods.
[0241] Additional multiphase character may also exist as a fine structure within the synthetic rubber-rich domains, with the A blocks forming one phase and the B blocks forming a second phase.
[0242] In one embodiment of the invention, one or both surfaces of the PSA layer are physically and / or chemically pretreated. For example, such pretreatment can be performed by plasma pretreatment. In the case where both surfaces of the PSA layer are pretreated, the pretreatment of each surface can be different, or in particular, both surfaces can have the same pretreatment.
[0243] Plasma treatment (more particularly low-pressure plasma treatment) is a known method for pretreating the surface of adhesives. Plasma leads to activation of the surface in the sense of higher reactivity. In this case, for example, there are chemical changes in the surface, allowing to influence the behavior of the adhesive with respect to polar and non-polar surfaces. This pretreatment is mainly concerned with surface phenomena.
[0244] The PSA layer of the invention is typically 10 to 200 μm thick, preferably 15 to 100 μm thick, and more particularly 25 to 60 μm thick.
[0245] d) Adhesive tape
[0246] In order that the adhesive tape can be easily and without residues again by stretching over a large range, they must have not only the above-mentioned adhesive properties, but also certain mechanical properties. Particularly advantageously, the ratio of tearing force to peeling force is greater than two, preferably greater than three. The peeling force is the force that must be consumed in order to peel the adhesive tape again from the adhesive portion by stretching over a large range in the bonding plane. The peeling force consists of the force required to peel the adhesive tape from the adhesive substrate as described above and the force that must be consumed in order to deform the adhesive tape. The force required to deform the adhesive tape depends on the thickness of the adhesive tape. On the contrary, within the range of the adhesive tape thickness considered, the force required for peeling is independent of the thickness of the adhesive tape.
[0247] It is therefore preferred that the adhesive tape has a peel force F of less than 60%, preferably less than 50%. 剥离 and the breaking force F 断裂 Implementation method of the ratio.
[0248] The carrier is preferably coated on at least one side, and more preferably on both sides, with a pressure-sensitive adhesive.The adhesive tape can thus be a single-sided tape or a double-sided tape, and is preferably double-sided.
[0249] The thickness of the adhesive tape can be selected according to the application. In a preferred embodiment, the adhesive tape has a thickness of 30 to 350 μm, preferably 30 to 250 μm and more preferably 50 to 200 μm.
[0250] e) Manufacturing method
[0251] A further subject matter of the present invention is a method for producing the adhesive tape according to the invention.
[0252] i) TPU-based carrier
[0253] In a first alternative, the process of the invention relates to a process for producing an adhesive tape according to the invention, wherein a crosslinked polyurethane is
[0254] (i) extruded onto a temporary support and combined on at least one side, preferably on both sides, with a layer of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer, or
[0255] (ii) extruded onto the layer of pressure-sensitive adhesive based on vinyl aromatic block copolymers to give a carrier which is preferably combined with a further layer of pressure-sensitive adhesive based on vinyl aromatic block copolymers on the side opposite to the pressure-sensitive adhesive layer,
[0256] Thus, an adhesive tape is obtained.
[0257] All ingredients of the TPU-based formulation to be produced are first dried in a pellet dryer and then supplied via metering openings and metering or conveying systems to a continuous mixing or conveying assembly with a mixing section. The temperature regime corresponds to the optimum conditions required for producing a homogeneous mixture.
[0258] The outlet of the continuous conveying assembly with a mixing section or mixing assembly, and / or further components for conveying the extrudate via a die or distributor channel to a preliminary shaping or directly to a coating unit, may have different configurations. For coating flat films, a slot die is suitable for the preliminary shaping of the extrudate or melt film. The extrudate or film can be deposited directly on a rotating roller, usually cooled (called a cooling roller), in which case the layer thickness can be additionally adjusted via the take-off speed. Alternatively, coating can be carried out directly on a preliminary material, such as a (temporary) carrier or a functional layer, such as more particularly a pressure-sensitive adhesive layer.
[0259] In a particularly advantageous embodiment of the method according to the invention, the pre-homogenized extrudate is shaped by a slot die to form a melt film and applied directly to a first adhesive layer which is arranged on a temporary carrier, for example a (siliconized) liner in particular. The prefabricated functional layer is preferably pre-supplied via a cooling roller using an unwinding station.
[0260] This assembly consisting of a temporary carrier (liner), an adhesive layer and a PU layer is preferably laminated to a second prefabricated adhesive layer on a temporary carrier, such as a release liner in particular, before being wound into a bundle (pack). The final product now consists of three layers of adhesive-PU carrier-adhesive sandwiched between two temporary carriers, such as liners in particular. Before being wound into a bundle, one temporary carrier (such as a liner in particular) can be removed.
[0261] This procedure has many advantages: particularly efficient production of multilayer products; improved composite strength / anchoring between adhesive or various types of carrier layers and TPU layers; avoidance of the often problematic intermediate step of transfer coating (TPU to release carrier). Thus, even particularly soft TPU products become easy to produce and no processing aids such as waxes and / or lubricants, coextruded support carriers or additional auxiliary liners of the type typically required when producing TPU carriers are required.
[0262] In the process of the present invention, it is also possible to use a TPU-based foamed carrier.
[0263] For this purpose, all ingredients of the TPU-based (after drying) formulation to be produced, including the unexpanded microspheres, are preferably supplied via metering holes and metering or delivery systems to a continuous mixing or delivery assembly with a mixing section. The temperature regime corresponds to the optimal conditions for producing a homogeneous mixture and foaming of the microspheres. Up to the outlet, a continuous counterpressure is preferably maintained to prevent premature expansion of the microspheres.
[0264] The outlet of the continuous conveying assembly with mixing section or mixing assembly and / or for conveying the extrudate for preliminary shaping or directly to the other parts of the coating unit via die head or distributor channel can have different configurations. In order to coat flat film, the slit die is suitable for the preliminary shaping of extrudate or melt film. Preferably, the reverse pressure set up in the coating process prevents the microspheres or expanded microspheres from breaking through the coated surface. In this way, rough surface can be prevented, and such surface causes the anchoring of the difference of pressure-sensitive adhesive layer again. Reverse pressure can be, for example, a pressure roller or a reverse roller on a coating roller, or directly applies in a calender. Here equally, preferably directly apply on preliminary material such as (temporary) carrier or the pressure-sensitive adhesive layer applied to a temporary carrier.
[0265] This assembly of temporary carrier (liner), adhesive layer and PU layer is preferably laminated on the opposite side to a second prefabricated adhesive layer on a temporary carrier, such as in particular a release liner or any other type of carrier layer, before being wound into a bundle.
[0266] The final product preferably consists of three layers of adhesive - foamed PU carrier - adhesive sandwiched between two temporary carriers such as liners. Before winding into bales, one temporary carrier (liner) can be removed. Direct coating onto the PSA layer has many advantages: particularly efficient production of multilayer products; improved composite strength / anchoring between adhesive and any kind of carrier layer or TPU layer; avoidance of the often problematic intermediate step of transfer coating (TPU to peel carrier). In this way, even particularly soft TPU products become easy to manufacture and do not require processing aids such as waxes and / or lubricants, coextruded support carriers or additional auxiliary liners typically required in the manufacture of TPU carriers.
[0267] Closed-cell TPU foams comprising microspheres are not commercially available, and therefore the process and the resulting carrier layer of the invention form the basis for an innovative product.
[0268] Further options for producing open-cell TPU foams are available: the addition of chemical blowing agents or the controlled injection of gases, ie physical blowing agents.
[0269] The chemical blowing agent can be added directly to the continuous conveying assembly with the mixing section together with the starting materials, or via one of the additional metering orifices. Processing and coating are preferably carried out as described above.
[0270] The gas can be injected into the extruder via additional metering holes into the melt mixture. The gas is preferably supplied in a regulated manner, allowing the gas fraction in the mixture and the resulting density to be regulated. Processing and coating are preferably performed as described above.
[0271] ii) PUD-based vectors
[0272] An alternative embodiment relates to a method for producing the adhesive tape according to the invention, wherein a polyurethane-based dispersion and a crosslinking agent are mixed.
[0273] (i) coated onto a temporary support or dried and the resulting support is combined on at least one side, preferably on both sides, with a layer of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer, or
[0274] (ii) coated onto the pressure-sensitive adhesive layer based on a vinyl aromatic block copolymer to obtain a carrier, which is preferably combined with an additional pressure-sensitive adhesive layer based on a vinyl aromatic block copolymer on the side opposite to the pressure-sensitive adhesive layer, and dried,
[0275] Thus, an adhesive tape is obtained.
[0276] In order to produce a homogeneous, bubble-free dispersion mixture, stirring devices suitable for the dispersion are recommended. Crosslinkers, thickeners and / or other additives are usually predispersed with water and then supplied to the PU dispersion in portions with continuous careful stirring.
[0277] During the stirring operation, vortexing or excessive speeds should be avoided to prevent unwanted introduction of air by stirring. It is recommended to prepare the blend several hours before coating to promote the escape of small air bubbles that have been introduced by stirring.
[0278] The coating can be carried out via different applicator systems, such as a doctor blade, a die or a distributor channel, etc. The coated PU dispersion is preferably dried via heat supply in a drying tunnel with different heating zones. The PU dispersion can be applied to a (temporary) carrier or directly to the PSA layer. After drying and before winding, a second PSA layer is preferably laminated to the opposite side, allowing a multilayer product to be manufactured in one step. The multilayer assembly thus manufactured is preferably wound to form a bundle. The liner or other auxiliary carrier can be removed in advance.
[0279] This procedure has many advantages: particularly efficient production of multilayer products; improved composite strength / anchoring between adhesive, carrier layer of any kind or PU layer; avoidance of the often problematic intermediate step of transfer coating (PU to release carrier).
[0280] The PU-based carrier layer from the dispersion or the adhesive tape comprising this layer can be subjected to a heat treatment at not less than 150° C. in order to optimize the tensile strength.
[0281] In a preferred embodiment, the production is carried out using a carrier based on a foamable PU dispersion.
[0282] In order to produce a uniform, bubble-free dispersion mixture that can be foamed with microspheres, a stirring device suitable for dispersion is recommended. Crosslinking agents, thickeners and / or other additives, as well as unexpanded microspheres are preferably pre-dispersed with water and then supplied to the PU dispersion in batches under continuous careful stirring. During the stirring operation, eddies or excessive speeds should be avoided to prevent unwanted introduction of air by stirring. It is recommended to prepare the blend several hours before coating to promote the escape of small bubbles that have been introduced by stirring.
[0283] The coating can be carried out via different applicator systems, such as a doctor blade, a die or a dispenser channel, etc. The coated PU dispersion is preferably dried via heat supply in a drying tunnel with different heating zones. The PU dispersion can be coated onto a (temporary) support or directly onto the PSA layer. After drying and before winding, a second PSA layer is preferably laminated onto the opposite side, allowing the production of a multilayer product in one step.
[0284] The multilayer components thus produced are preferably wound into bundles. The liner or other auxiliary carriers may have been removed beforehand. This procedure has many advantages: particularly efficient production of multilayer products; improved composite strength / anchoring between adhesive or any kind of carrier layer or PU layer; avoidance of the often problematic intermediate step of transfer coating (PU to peel carrier).
[0285] In a further operating step, the entire assembly or individual layers of the foamable PU carrier are partially or completely foamed by further supply of heat through a heating tunnel or a heatable contact roller, and / or the microspheres expand. The sandwiching of the foamable PU carrier with the carrier, auxiliary liner or PSA layer prevents the expanded microspheres from breaking through the surface and thus achieves good bond strength between the layers. As a result of foaming with microspheres, a closed-cell PU foam is produced.
[0286] In a further embodiment, the PU dispersion can be mixed with pre-expanded microspheres, likewise resulting in a foamed PU carrier.By laminating at least one PSA layer, single-sided or double-sided adhesive tapes can likewise be produced.
[0287] Open-cell PU foams can also be produced by purposefully introducing air through stirring (known as foaming). Here, the beating-in of air is brought about in a controlled manner by stirring equipment suitable for the purpose and specific stirring conditions. The further production operations are preferably carried out analogously to the above-described method.
[0288] A particular feature of the adhesive tape of the invention is that it can be peeled off again without residue or destruction with relatively low expenditure of force, thus making it particularly suitable for the production of electronic components. Therefore, a further subject of the invention is the use of the adhesive tape of the invention for bonding components in electronic devices.
[0289] A further subject matter of the invention is an electronic device comprising a first component and a second component bonded together using the adhesive tape according to the invention.
[0290] The invention is explained in more detail below by means of a number of illustrative tapes.Particularly advantageous implementations of the invention are explained in more detail by means of the examples described below, without any intention to unnecessarily restrict the invention thereby.
[0291] Example
[0292] Table 1 shows the (raw) materials used in the (comparative) examples. Tables 2 and 3 show the formulations of the carriers and adhesive layers produced in the (comparative) examples.
[0293] Table 1: (Comparative) Materials Used in Examples
[0294]
[0295]
[0296] Table 2: (Comparative) Formulations of the carriers produced in the examples
[0297]
[0298]
[0299] Table 3: (Comparative) Formulations of Adhesive Layers Made in Examples
[0300]
[0301] Table 4 shows the structure of adhesive tapes of (comparative) examples, which were formed by combining the above-mentioned carrier from Table 2 and the pressure-sensitive adhesive (PSA) from Table 3. The adhesive tapes were each double-sided, meaning that one PSA layer was arranged on each side of the carrier.
[0302] Table 4: Structure of adhesive tape of (comparative) example
[0303]
[0304] Each tape was manufactured as follows:
[0305] Production of an adhesive tape with a TPU core layer TPU 1 (Example 1):
[0306] The purchased TPU core layer TPU 1 containing processing aids was laminated on both sides with the PSA layer A. Before laminating the TPU core layer TPU1 with the PSA layer, the supporting PE carrier was removed from the TPU core layer in each case. The PSA layer had the same thickness on both sides of the carrier. The microspheres in the PSA layer A had not yet expanded, i.e. the PSA layer A had not yet foamed.
[0307] The overall assembly of carrier layer and PSA layer was subjected in each case to a further heat treatment step for better anchoring and foaming of the PSA layer. For this treatment, the wound material was passed through a tunnel system with a temperature profile comprising three zones of 120° C. / 135° C. / 170° C. at a belt speed of 6 m / min before being wound again. The result was a foamed double-sided adhesive tape with a TPU core layer TPU 1.
[0308] Production of tapes with PUD core layers PUD 1 to PUD 6 (Examples 2 to 9):
[0309] If a thickener is used, a polyurethane dispersion (PU dispersion, PUD) is blended with the thickener by a conventional vertical agitator device with a Visco Jet agitator. In this case, the polyurethane dispersion is introduced into a container of sufficient size and carefully stirred. In the entire blending operation, vortex formation or any air introduced by stirring should be avoided. All other ingredients, such as crosslinker solution, dye solution and thickener solution, are supplied to the initially introduced polyurethane dispersion in batches under continuous stirring. In order to obtain a uniform mixture, a stirring time of at least 30 minutes is observed. The thickened polyurethane dispersion thus prepared is ideally prepared one day before coating. This allows the small bubbles introduced by stirring to escape. The blended polyurethane dispersion or the polyurethane dispersion without the addition of thickener can then be coated on a coating system with a drying tunnel, i.e., an applicator system. Table 5 shows the relevant parameters of the coating system and the drying tunnel. Except for the surfactant, the manufactured PUD core layer does not contain a processing aid and does not have a crystalline superstructure.
[0310] Table 5: Relevant parameters of coating system and drying tunnel
[0311]
[0312] Using two unwinders, a PET carrier with a release function or a prefabricated functional layer, i.e. a PSA layer, on a PET carrier with a release function is provided. It has proven useful to build up the desired layer thickness on the PET carrier and then switch to the prefabricated PSA layer and apply it directly. Before winding, a second PSA layer with the same thickness as the first PSA layer is laminated to it using an adjustable contact-pressure roller.
[0313] The resulting three-layer product is then wound up. The integral assembly of PU carrier and PSA layer is subjected to a further heat treatment step to optimize the tensile strength of the carrier, thereby improving anchoring, and to foam the PSA layer if it contains unexpanded microspheres. To this end, the wound material is passed through the same tunnel system with a temperature profile comprising three zones of 120° C. / 135° C. / 170° C. at a belt speed of 6 m / min and then wound up again. This produces double-sided tapes with PUD core layers PUD 1 to PUD 6.
[0314] result:
[0315] Table 6 shows the mechanical properties of the produced tapes and the carriers they comprise.
[0316] Table 6: Mechanical properties of adhesive tapes
[0317]
[0318] Embodiment 2-7:
[0319] The use of core layers (carriers) based on crosslinked PU carriers, including in particular those based on crosslinked PUD carriers, has proven to be particularly advantageous according to the invention, since particularly advantageous forces F at 400% elongation can be set here. 400% The ratio between the typical extension range during the peeling operation in the component and the ultimate tensile strength (ultimate tensile strength). This means that the force F during the peeling operation 400% It is particularly low compared to comparative example 1, while having a high ultimate tensile strength, which in turn leads to very good tear resistance. Using the carrier according to the invention, greater impact properties can also be achieved.
[0320] Surprisingly and unforeseeable to the person skilled in the art, it has been possible to significantly increase the ultimate tensile strength again by using a crosslinking agent while having a low F 400% And maintain good impact properties, which leads to further improved tear resistance. Then, relative to Comparative Examples 2 and 3 in which no crosslinking agent is used, a further increase in ultimate tensile strength is achieved without F 400% any significant increase in .
[0321] Example 8 (Comparison-Comparative Example)
[0322] The use of PSAs based on styrene block copolymers has proven to be advantageous, especially in combination with a carrier crosslinked according to the invention, as shown in Example 8. The use of PSAs based on acrylates gave much poorer results, especially with regard to tear resistance.
[0323] Example 9
[0324] As shown in Example 9, the use of a PSA based on a polymer blend (polymer based on vinyl aromatic block polymer and acrylate) has proven to be advantageous, especially in combination with a support crosslinked according to the invention.
[0325] Test Method
[0326] Unless stated otherwise, all measurements were carried out at 23° C. and 50% relative air humidity. The mechanical and adhesive data were determined as follows:
[0327] Tear test by tensile tester Zwick
[0328] In the tear test, a first test plate of polyethylene and a second test plate of steel were used. 67215 double sided tape wrap, to which the "battery film" has then been applied. The 67215 tape has a total thickness of 150 μm and comprises a polyurethane carrier on each side of which a foamed pressure-sensitive adhesive layer based on a vinyl aromatic block copolymer is provided. The "battery film" is an aluminum-laminated polymer film from DNP with a thickness of 88 μm (this film is typically used in the manufacture of lithium polymer batteries).
[0329] From the adhesive tape to be checked, a specimen with a width of 8 mm and a length of 60 mm is die-cut or laser-cut. These specimens are pasted on the first test plate of the above-mentioned battery film-wrapped polyethylene in a length of 50 mm to leave a tab of 10 mm in length. The tab is covered with 36 μm PET on both sides. After cleaning with acetone and preconditioning at 23° C. and 50% relative air humidity for 1 to no more than 10 minutes, a second test plate of steel is pasted on the reverse side of the adhesive tape (i.e., the specimen) so that the two test plates are flush with each other, i.e., congruent. A 4 kg roller is run 10 times (5 times back and forth) on the composite on the reverse side of the steel plate. After an attachment time of at least 4 hours at 23° C. and 50% relative air humidity, the strip is peeled off from the adhesive joint at an angle of 90° via the edge of the first test plate of the battery film-wrapped polyethylene using the tab by a tensile tester (from Zwick) at a constant speed of 800 mm / min. Here, the specimen is fixed with an angle-adjustable adapter and the tab is clamped vertically in the middle of the jaws.
[0330] The measurement is performed at an angle of 90°, during which the force required to peel the sample off is recorded by the tensile tester, which is called the peel force F. 剥离 The measurement is terminated as soon as the sample is completely peeled off between the two test plates or the sample tears during the measurement. At least 6 measurements are carried out for each specimen. The test conditions are 23°C and 50% relative air humidity.
[0331] Results report:
[0332] Tear at 90° - The test is considered to have passed if less than 20% of the specimen tears during the peeling operation.
[0333] F 剥离 90°[N / cm]——The force required to peel the sample from the adhesive joint at an angle of 90° (peel force)
[0334] Tensile testing with Zwick tensile testing machine
[0335] Strips with a width of 15 mm and a length of about 150 mm are cut from the sample to be tested (adhesive tape, i.e. a carrier preferably provided with adhesive on both sides, or just a simple (plain) carrier) in the longitudinal direction using a strip cutter or a razor blade. The sample, which has been preconditioned under test conditions for 24 h, is clamped at a right angle between the jaws with a clamping length of 10 mm and stretched at a speed of 800 mm / min until it tears. The break should occur approximately in the middle of the strip. If the break is close to the jaws (closer than 1 cm), the value should be rejected and another strip should be tested instead. 5 measurements are carried out for each sample variant. The test conditions are 23° C. and 50% relative air humidity. The measurement is in accordance with EN ISO 527.
[0336] Results report:
[0337] F x% [N / cm],[N / mm 2 ] - force at x% elongation
[0338] F 断裂 [N / cm],[N / mm 2 ]-The force at which the sample tears / breaks (i.e. tear strength)
[0339] EB[%] - elongation at break, i.e. the percentage of elongation when the sample is torn / broken
[0340] Through-penetration toughness, DuPont test in the z-plane
[0341] A square sample in the shape of a frame (external dimensions 33mm x 33mm; border width 2.0mm; internal dimensions (cut-out window) 29mm x 29mm) was cut from the tape to be inspected. The sample was adhered to a polycarbonate (PC) frame (external dimensions 45mm x 45mm; border width 10mm; internal dimensions (cut-out window) 25mm x 25mm; thickness 3mm). A 35mm x 35mm PC window was adhered to the other side of the double-sided tape. The PC frame, tape frame and PC window were bonded so that the geometric center and diagonal lines overlapped each other (corner to corner). The bonding area was 248mm 2 The bonds were subjected to a pressure of 248 N for 5 seconds and stored at 23° C. / 50% relative humidity for 24 hours.
[0342] Immediately after storage, the adhesive composite consisting of the PC frame, the tape and the PC window is supported in the sample holder with the protruding edge of the PC frame so that the composite is oriented horizontally. The PC frame is laid flat on the protruding edge of the sample holder so that the PC window floats freely (held by the tape sample) below the PC frame. The sample holder is then inserted centrally in the predetermined socket of the "DuPont Impact Tester". A punch weighing 150 g is used in such a way that a circular impact geometry with a diameter of 24 mm is impacted centrally and flushly on the face of the PC window freely accessible from above.
[0343] A weight with a mass of 150 g guided on two guide rods was dropped vertically from a height of 5 cm onto the composite composed of the sample holder, sample and punch arranged in this way (test conditions: 23° C., 50% relative humidity). The height from which the weight was dropped was increased in 5 cm steps until the impact energy introduced destroyed the sample as a result of the penetration stress and the PC window was separated from the PC frame.
[0344] In order to be able to compare experiments with different samples, the energy was calculated as follows:
[0345] Energy E[J] = height [m] * mass of the object [kg] * 9.81kg / m * s 2
[0346] Five samples were tested for each product and the average energy was reported as an indicator for penetration resistance.
[0347] Shore A Hardness
[0348] The Shore A hardness of the samples was measured according to ASTM D2240.
[0349] Modulus at 100% elongation, elongation at break
[0350] The modulus at 100% elongation or the elongation at break of the specimens was determined according to DIN 53504.
[0351] thickness
[0352] The thickness of the adhesive layer can be determined by measuring the thickness of a segment of such adhesive layer applied to the liner defined with respect to its length and width, minus the (known or separately measurable) thickness of a segment of the same size of the liner used. The thickness of the adhesive layer can be determined with the aid of a commercial thickness measuring instrument (caliper test instrument) with an accuracy of less than 1 μm deviation. If variations in thickness are found, the average of the measurements at at least three representative sites is reported, i.e. more particularly not measuring at wrinkles, creases, spots, etc.
[0353] The thickness of the adhesive tape (adhesive strip) or carrier can also be determined in a similar manner, as for the thickness of the adhesive layer described above, with the aid of a commercial thickness measuring instrument (caliper test instrument) having an accuracy of less than 1 μm deviation. If variations in thickness are found, the average value of the measurements at at least three representative locations is reported, i.e. more particularly not at wrinkles, folds, spots, etc.
[0354] density
[0355] The density of the unfoamed and foamed adhesive layers was determined by forming the quotient of the applied mass and the thickness of the adhesive layer applied to the liner.
[0356] The applied mass can be determined by determining the mass of a segment of such adhesive layer applied to the liner defined with respect to its length and width and subtracting the (known or individually determinable) mass of a segment of the same dimensions of the liner used.
[0357] The thickness of the adhesive layer can be determined by determining the thickness of a segment of such adhesive layer applied to the liner defined with respect to its length and width, minus the (known or separately measurable) thickness of a segment of the same size as the liner used. The thickness of the adhesive layer can be determined with the aid of a commercial thickness measuring instrument (caliper test instrument) with an accuracy of less than 1 μm deviation. If variations in thickness are found, the average of the measurements at at least three representative sites is reported, i.e. more particularly not measuring at wrinkles, creases, spots, etc.
[0358] The density of the carrier can be determined similarly.
[0359] Molecular weight n 、M w
[0360] In this document, the number average molecular weight M n and weight average molecular weight M w The reported values relate to the determination by gel permeation chromatography (GPC). The determination is carried out using 100 μl of clarified filtered sample (sample concentration 4 g / l). The eluent used is tetrahydrofuran with 0.1% by volume of trifluoroacetic acid. The measurement is carried out at 25° C. The precolumn used is the following column: PSS-SDV type, 5 μm, 8.0mm x 50mm (The values here and below are in the following order: type, particle size, porosity, inner diameter*length; ). For separation, the following column combination was used: PSS-SDV type, 5 μm, and and Each had 8.0 mm x 300 mm (column from Polymer Standards Service; detection by means of a Shodex RI71 differential refractometer). The flow rate was 1.0 ml / min. In the case of polar molecules, such as starting materials for polyurethanes, calibration was performed against PMMA standards (polymethyl methacrylate calibration) and in other cases against PS standards (polystyrene calibration).
[0361] Softening temperature of tackifying resin
[0362] The tackifying resin softening temperature is determined according to a method known as the Ring & Ball method and standardized according to ASTM E28.
[0363] DAPC
[0364] 5.0 g of the test substance (tackifier resin sample to be checked) are weighed into a dry test tube and 5.0 g of xylene (isomer mixture, CAS [1330-20-7], ≥98.5%, Sigma-Aldrich #320579 or equivalent) are added. The test substance is dissolved at 130° C. and then cooled to 80° C. Any xylene that escapes is made up with fresh xylene so that 5.0 g of xylene are present again. Subsequently, 5.0 g of diacetone alcohol (4-hydroxy-4-methyl-2-pentanone, CAS [123-42-2], 99%, Aldrich #H41544 or equivalent) are added. The test tube is shaken until the test substance is completely dissolved. To this end, the solution is heated to 100° C. The test tube containing the resin solution is then introduced into a Novomatics Chemotronic Cool cloud point measuring instrument and heated therein to 110° C. It is cooled at a cooling rate of 1.0 K / min. The turbidity point is detected optically. For this purpose, the temperature at which the turbidity of the solution is 70% is recorded. The results are reported in ° C. The lower the DACP value, the more polar the test substance.
Claims
1. Tapes that can be peeled off by stretching, including: a) at least one carrier based on a crosslinked polyurethane; and b) at least one layer of pressure-sensitive adhesive based on vinyl aromatic block copolymers, wherein the polyurethane is crosslinked using a crosslinker based on aziridine, carbodiimide, melamine or isocyanate, and the crosslinker is used in an amount of 0.5 to 10% by weight, in each case based on the total weight of the carrier, wherein the total proportion of the vinyl aromatic block copolymers is from 15 to 60% by weight, based on the entire pressure-sensitive adhesive; Where the adhesive tape has a peel force F of less than 60% 剥离 and the breaking force F 断裂 Ratio.
2. The adhesive tape according to claim 1, characterized in that The polyurethane is a polyurethane TPU prepared by extrusion or a polyurethane PUD prepared from a dispersion.
3. The adhesive tape according to claim 1 or 2, characterized in that Polyurethanes are crosslinked using isocyanate-based crosslinkers.
4. The adhesive tape according to claim 1 or 2, characterized in that The crosslinkers are used in amounts of 1.0 to 8.0% by weight, in each case based on the total weight of the carrier.
5. The adhesive tape according to claim 4, characterized in that The crosslinkers are used in amounts of 1.5 to 5% by weight, in each case based on the total weight of the carrier.
6. The adhesive tape according to claim 1 or 2, characterized in that The carrier is foamed.
7. The adhesive tape according to claim 6, characterized in that The carrier is foamed by microspheres.
8. The adhesive tape according to claim 1 or 2, characterized in that The vinyl aromatic block copolymer is a styrene-butadiene block copolymer.
9. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive layer is foamed.
10. The adhesive tape according to claim 9, characterized in that The pressure-sensitive adhesive layer is foamed by microspheres.
11. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive layers are arranged on both sides of the carrier, and the adhesive tape is therefore a double-sided adhesive tape.
12. The adhesive tape according to claim 1 or 2, characterized in that The adhesive tape has a thickness of 30 to 350 μm.
13. The adhesive tape according to claim 12, characterized in that The adhesive tape has a thickness of 30 to 250 μm.
14. The adhesive tape according to claim 12, characterized in that The adhesive tape has a thickness of 50 to 200 μm.
15. The adhesive tape according to claim 1, characterized in that The tape has a peel force F of less than 50% 剥离 and the breaking force F 断裂 Ratio.
16. The adhesive tape according to claim 1 or 2, characterized in that The carrier has a force F at 400% extension of at most 45%. 400% and the breaking force F 断裂 Ratio.
17. The adhesive tape according to claim 16, characterized in that The carrier has a force F at 400% extension of at most 40%. 400% and the breaking force F 断裂 Ratio.
18. The adhesive tape according to claim 1 or 2, characterized in that The carrier layer has a longitudinal elongation at break of at least 600%.
19. The adhesive tape according to claim 1 or 2, characterized in that The carrier layer has a longitudinal elongation at break of at least 800%.
20. The adhesive tape according to claim 1 or 2, characterized in that The carrier of the adhesive tape comprises at least one layer based on crosslinked thermoplastic polyurethane, which has been produced by extrusion.
21. The adhesive tape according to claim 1 or 2, characterized in that The carrier of the adhesive tape comprises exactly one layer based on cross-linked thermoplastic polyurethane, which has been produced by extrusion.
22. The adhesive tape according to claim 20, characterized in that Thermoplastic polyurethanes are the reaction product of a reaction mixture comprising at least one diisocyanate, at least one polyester polyol or polyether polyol, a crosslinker, and optionally at least one chain extender.
23. The adhesive tape according to claim 22, characterized in that The diisocyanate is diphenylmethane 4,4'-diisocyanate MDI, hexane diisocyanate HDI, isophorone diisocyanate IPDI or hexamethylene diisocyanate HMDI.
24. The adhesive tape according to claim 22, characterized in that Polyester polyols are polyalkylene adipates.
25. The adhesive tape according to claim 20, characterized in that The layer based on crosslinked thermoplastic polyurethane contains no additives.
26. The adhesive tape according to claim 25, characterized in that The additives are selected from antiblocking agents and waxes.
27. The adhesive tape according to claim 20, characterized in that Polyurethane does not have a crystalline superstructure.
28. The adhesive tape according to claim 1 or 2, characterized in that The carrier of the adhesive tape comprises at least one layer based on a crosslinked polyurethane which has been produced in dispersion using a crosslinker.
29. The adhesive tape according to claim 1 or 2, characterized in that The carrier of the adhesive tape comprises exactly one layer based on a crosslinked polyurethane, which has been produced as a dispersion using a crosslinker.
30. The adhesive tape according to claim 28, characterized in that The polyurethane is an aliphatic polyester-polyurethane or an aliphatic polyether-polyurethane.
31. The adhesive tape according to claim 28, characterized in that Polyurethane dispersions include the following dispersions, optionally in combination: a) anionically stabilized aliphatic polyester-polyurethane dispersions; b) anionically stabilized aliphatic polyether-polyurethane dispersions; c) anionically stabilized aliphatic polycarbonate-polyester-polyurethane dispersions; d) Anionically stabilized polycarbonate-polyurethane dispersions.
32. The adhesive tape according to claim 31, characterized in that The starting mixture for the carrier additionally comprises at least one further dispersion selected from polyurethane dispersions, polyurethane dispersions whose polyol component comprises comonomers having a flame-retardant effect, synthetic rubber dispersions, natural rubber dispersions and polyacrylate dispersions.
33. The adhesive tape according to claim 28, characterized in that The polyurethane-based carrier layer from the dispersion contains no additives.
34. The adhesive tape according to claim 33, characterized in that The additives are selected from antiblocking agents and waxes.
35. The adhesive tape according to claim 28, characterized in that Polyurethane does not have a crystalline superstructure.
36. The adhesive tape according to claim 28, characterized in that The polyurethane-based carrier layer from the dispersion or the adhesive tape comprising this layer is subjected to a heat treatment at not less than 150°C.
37. The adhesive tape according to claim 1 or 2, characterized in that The crosslinking agent is an isocyanate.
38. The adhesive tape according to claim 37, characterized in that The crosslinking agent is a blocked polyisocyanate.
39. The adhesive tape according to claim 38, characterized in that The crosslinking agent is a blocked aliphatic polyisocyanate.
40. The adhesive tape according to claim 38, characterized in that The polyisocyanate was hexamethylene diisocyanate.
41. The adhesive tape according to claim 38, characterized in that The polyisocyanate is a trimer of hexamethylene diisocyanate.
42. The adhesive tape according to claim 1, characterized in that The total proportion of the vinylaromatic block copolymers is from 20 to 50% by weight, based on the total pressure-sensitive adhesive.
43. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive layer is composed of a pressure-sensitive adhesive formed based on a vinyl aromatic block copolymer and a tackifier resin, wherein the tackifier resin is selected to have a diacetone alcohol cloud point of greater than -20°C and a softening temperature of not less than 70°C determined by a ring and ball method to an extent of at least 30% by weight, based on the total tackifier resin content.
44. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive consists of the following ingredients: - Styrene block copolymer 20 to 75 wt% - Tackifier resin 24.6 wt% to 60 wt% - Microspheres 0.2% to 10% by weight - Additives 0.2 to 10% by weight.
45. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive consists of the following ingredients: - Styrene block copolymer 35 to 65 wt% - Tackifier resin 34.6 wt% to 45 wt% - Microspheres 0.2% to 10% by weight - Additives 0.2 to 10% by weight.
46. The adhesive tape according to claim 1 or 2, characterized in that The pressure-sensitive adhesive layer is based on a blend of vinyl aromatic block copolymers and polyacrylates.
47. The adhesive tape according to claim 46, characterized in that Vinyl aromatic block copolymers are immiscible with polyacrylates.
48. A process for producing an adhesive tape according to any one of claims 1 to 47, wherein a crosslinkable polyurethane (i) extruded onto a temporary support and combined on at least one side with a layer of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer, or (ii) Extrusion onto a vinyl aromatic block copolymer-based pressure-sensitive adhesive layer to obtain a carrier, thereby obtaining an adhesive tape.
49. The method according to claim 48, characterized in that The crosslinkable polyurethane (i) is extruded onto a temporary support and combined on both sides with a layer of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer to give an adhesive tape.
50. The method according to claim 48, characterized in that The crosslinkable polyurethane (ii) is extruded onto the vinyl aromatic block copolymer-based pressure-sensitive adhesive layer to obtain a carrier, which is combined with another vinyl aromatic block copolymer-based pressure-sensitive adhesive layer on the side opposite to the pressure-sensitive adhesive layer to obtain an adhesive tape.
51. A process for producing an adhesive tape according to any one of claims 1 to 47, wherein a polyurethane-based dispersion and a crosslinking agent are mixed. (i) coated onto a temporary support or dried and the resulting support is combined on at least one side with a layer of a pressure-sensitive adhesive based on a vinyl aromatic block copolymer, or (ii) coating on a vinyl aromatic block copolymer-based pressure-sensitive adhesive layer to obtain a carrier and drying, Thus, an adhesive tape is obtained.
52. The method according to claim 51, characterized in that The polyurethane-based dispersion and the crosslinking agent (i) are coated onto a temporary support or dried, and the resulting support is combined on both sides with a vinyl aromatic block copolymer-based pressure-sensitive adhesive layer to give an adhesive tape.
53. The method according to claim 51, characterized in that The polyurethane-based dispersion and the crosslinking agent (ii) are applied to the vinyl aromatic block copolymer-based pressure-sensitive adhesive layer to obtain a carrier, which is combined with another vinyl aromatic block copolymer-based pressure-sensitive adhesive layer on the side opposite to the pressure-sensitive adhesive layer to obtain an adhesive tape and dried.
54. Use of an adhesive tape according to any one of claims 1 to 47 for bonding components in electronic devices.
55. An electronic device comprising a first component and a second component bonded with an adhesive tape according to any one of claims 1 to 47.
Citation Information
Patent Citations
removable adhesive strip
DE102015206076A1
removable adhesive strip
DE102016223852A1
Stretch releasable adhesive article, usage and manufacturing the same
WO2015135134A1
Detachable adhesive strip
CN104919017A
Removable contact-adhesive tape
CN108541268A